Electrophotographic device, process cartridge
The electrophotographic device employs a cleaning blade with controlled elastic modulus and toner particle additives to stabilize cleaning performance and prevent startup streaks, addressing issues of toner fusion and image defects in high-temperature, high-humidity environments.
Patent Information
- Application Number
- JP2021064938
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-06
- Publication Date
- 2025-01-06
- Estimated Expiration
- 2041-04-06
AI Technical Summary
Existing toner technologies face challenges in maintaining stable cleaning performance and preventing startup streaks during high-speed printing, especially in high-temperature and high-humidity environments, due to issues with toner fluidity, solid followability, and chargeability, as well as deteriorating cleaning performance and toner fusion to the electrophotographic photoreceptor.
The electrophotographic device incorporates a cleaning blade with a polyurethane elastic member having specific elastic modulus and hardness variations, and toner particles with controlled external additives distribution to ensure uniform force application and prevent toner fusion, thereby stabilizing cleaning performance and reducing startup streaks.
The solution provides stable cleaning performance and suppresses startup streaks during the latter half of durability in high-temperature, high-humidity conditions by ensuring uniform force application and preventing toner fusion to the photoreceptor, enhancing image quality and durability.
Smart Images

Figure 0007608246000005 
Figure 0007608246000006 
Figure 0007608246000007
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a toner for developing an electrostatic charge image (electrostatic latent image) used in an image forming method such as electrophotography and electrostatic printing, an electrophotographic photoreceptor, and a process cartridge and an electrophotographic apparatus having the electrophotographic photoreceptor. [Background technology]
[0002] In recent years, there has been a demand for copiers and printers to operate at higher speeds and have stable high image quality. Toners are increasingly required to have high durability that can withstand higher speeds, a long life, and the ability to stabilize image quality. As a technology for improving the durability of toners, Patent Document 1 discloses a toner in which a thermosetting resin is contained in an encapsulating material having a capsule membrane hardness of 1 N / m or more and less than 3 N / m. The idea is to enable the toner to withstand strong shear.
[0003] On the other hand, as a method for stabilizing image quality with a long life, it has been proposed to use a cleaning blade to stably remove the toner remaining on the surface of an electrophotographic photoreceptor (hereinafter sometimes simply referred to as "photoreceptor") after transfer. For example, Patent Document 2 discloses a cleaning blade containing a polyurethane material containing a hard segment and a soft segment. Such a cleaning blade is composed of a polyurethane member in which the area ratio of hard segment aggregates having a diameter in the range of 0.3 μm to 0.7 μm in diameter in the cross section is 2% to 10%. This discloses a method for stably cleaning toner while achieving both chipping resistance and abrasion resistance.
[0004] In addition, toner that has not been removed from the photoconductor by cleaning (residual toner) stagnates or accumulates on the photoconductor, causing various image defects. Among the image defects that occur in this way, there is a strong demand for improvement of start-up streaks, which appear as colored streaks in the image. The start-up streaks are described below.
[0005] Considering the behavior of the electrophotographic photoreceptor and the cleaning blade during printing, agglomerates of transfer residual toner are formed at the tip of the cleaning blade by printing many sheets. If such agglomerates are present, the agglomerates are pressed against the electrophotographic photoreceptor by the pressure of the contact portion of the cleaning blade with the electrophotographic photoreceptor when printing is stopped, and the agglomerates are likely to fuse to the electrophotographic photoreceptor. If printing is attempted again in this state, some of the agglomerates fused to the electrophotographic photoreceptor slip through the cleaning blade and transfer to the charging member, causing poor charging and disturbing the latent image on the photoreceptor. Then, every time the charging member rotates two or three times, image defects due to poor charging occur for each rotation period of the charging member due to the same cause. Since this phenomenon occurs at the start of printing after the printing is stopped, the image defects caused by this phenomenon are called start-up streaks. Patent Document 3 proposes improving start-up streaks by using fatty acid metal salts. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2015-141360 A [Patent Document 2] JP 2016-14740 A [Patent Document 3] JP 2011-47988 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, in the toner described in Patent Document 3, the fluidity of the toner decreases in the latter half of the running test. This may result in problems associated with reduced solid image coverage and poor toner charging properties. Furthermore, even when the technologies of Patent Documents 1 and 2 are used, in the high-speed printing processes required in recent years, it has become clear that cleaning performance decreases in the latter half of a durability test in a high-temperature environment, making it difficult to prevent the occurrence of start-up streaks caused by toner fusing to an electrophotographic photosensitive member.
[0008] The present disclosure provides an electrophotographic apparatus and a process cartridge that can provide stable cleaning performance even during endurance use and can prevent the occurrence of starting streaks in the latter half of endurance use under a high-temperature, high-humidity environment. [Means for solving the problem]
[0009] The electrophotographic apparatus of the present disclosure is an electrophotographic photoreceptor having a support and a photosensitive layer on the support; a charging means for charging the surface of the electrophotographic photoreceptor; an exposure means for forming a latent image on the surface of the electrophotographic photoreceptor by irradiating the surface of the electrophotographic photoreceptor with exposure light; a developing means having a toner and for developing the latent image with the toner to form a toner image on the surface of the electrophotographic photoreceptor; a transfer means for transferring the toner image onto a transfer material; and Cleaning blade In an electrophotographic apparatus having The cleaning blade is An elastic member including polyurethane; A support member that supports the elastic member; Equipped with the cleaning blade is disposed so that a part of the elastic member is in contact with the surface of the electrophotographic photoreceptor, When the side of the cleaning blade that contacts the surface of the electrophotographic photoreceptor is defined as the tip side of the cleaning blade, The elastic member has at least the tip side, a main surface facing the surface of the electrophotographic photoreceptor; a tip surface which forms a tip edge together with the main surface; The plate shape has Assuming that a first line segment is drawn on the tip surface in parallel to the tip edge, at a distance of 10 μm from the tip edge, and of the same length as the tip edge, The length of the first line segment is L, On the first line segment, The point (1 / 10)L from one end of the first line segment is called P1. The point (2 / 10)L from one end of the first line segment is called P2. The point (3 / 10)L from one end of the first line segment is called P3. A point (4 / 10)L from one end of the first line segment is called P4. The point (5 / 10)L from one end of the first line segment is P5. The point (6 / 10)L from one end of the first line segment is P6. The point (7 / 10)L from one end of the first line segment is P7. The point (8 / 10)L from one end of the first line segment is P8. When the point P9 is (9 / 10)L from one end of the first line segment, When a total of 630 points are taken on the first line segment with a pitch of 1 μm, with each of the points P1 to P9 being the center, and the elastic modulus is measured at each of the 630 points using a scanning probe microscope, the average value of the elastic modulus is 15 MPa or more and 470 MPa or less, and The coefficient of variation of the elastic modulus is 7.0% or less, The Martens hardness of the elastic member measured at the position P5 is defined as HM1, Assuming that a bisector of an angle between the main surface and the tip surface is drawn on a cross section of the elastic member that is perpendicular to the tip surface and the tip edge including P5, the Martens hardness of the elastic member measured at a position on the bisector that is 500 μm away from the tip edge is HM2, |HM1-HM2| is 0.30N / mm 2 is as follows: The toner contains toner particles and an external additive, The number average particle size of the primary particles of the external additive is 5 nm or more and 25 nm or less, a coverage rate X1 of the surface of the toner particles by the external additive as measured by an X-ray photoelectron spectrometer is 50 area % or more and 85 area % or less; When the theoretical coverage rate of the surface of the toner particle by the external additive is X2, the diffusion index represented by the following formula (1) satisfies the following formula (2): (1) Diffusion index = X1 / X2 (2) Diffusion index ≧-0.0042×X1+0.60 It is characterized by:
[0010] The process cartridge of the present disclosure is an electrophotographic photoreceptor having a support and a photosensitive layer on the support; a developing means having a toner and for forming a toner image on the surface of the electrophotographic photoreceptor by developing a latent image formed on the surface of the electrophotographic photoreceptor with the toner; and Cleaning blade A process cartridge which is detachably mountable to a main body of an electrophotographic apparatus, The cleaning blade is An elastic member including polyurethane; A support member that supports the elastic member; Equipped with the cleaning blade is disposed so that a part of the elastic member is in contact with the surface of the electrophotographic photoreceptor, When the side of the cleaning blade that contacts the surface of the electrophotographic photoreceptor is defined as the tip side of the cleaning blade, The elastic member has at least the tip side, a main surface facing the surface of the electrophotographic photoreceptor; a tip surface which forms a tip edge together with the main surface; The plate shape has Assuming that a first line segment is drawn on the tip surface in parallel to the tip edge, at a distance of 10 μm from the tip edge, and of the same length as the tip edge, The length of the first line segment is L, On the first line segment, The point (1 / 10)L from one end of the first line segment is called P1. The point (2 / 10)L from one end of the first line segment is called P2. The point (3 / 10)L from one end of the first line segment is called P3. A point (4 / 10)L from one end of the first line segment is called P4. The point (5 / 10)L from one end of the first line segment is P5. The point (6 / 10)L from one end of the first line segment is P6. The point (7 / 10)L from one end of the first line segment is P7. The point (8 / 10)L from one end of the first line segment is P8. When the point P9 is (9 / 10)L from one end of the first line segment, When a total of 630 points are taken on the first line segment with a pitch of 1 μm, with each of the points P1 to P9 being the center, and the elastic modulus is measured at each of the 630 points using a scanning probe microscope, the average value of the elastic modulus is 15 MPa or more and 470 MPa or less, and The coefficient of variation of the elastic modulus is 7.0% or less, The Martens hardness of the elastic member measured at the position P5 is defined as HM1, Assuming that a bisector of an angle between the main surface and the tip surface is drawn on a cross section of the elastic member that is perpendicular to the tip surface and the tip edge including P5, the Martens hardness of the elastic member measured at a position on the bisector that is 500 μm away from the tip edge is HM2, |HM1-HM2| is 0.30N / mm 2 is as follows: The toner contains toner particles and an external additive, The number average particle size of the primary particles of the external additive is 5 nm or more and 25 nm or less, a coverage rate X1 of the surface of the toner particles by the external additive as measured by an X-ray photoelectron spectrometer is 50 area % or more and 85 area % or less; When the theoretical coverage rate of the surface of the toner particle by the external additive is X2, the diffusion index represented by the following formula (1) satisfies the following formula (2): (1) Diffusion index = X1 / X2 (2) Diffusion index ≧-0.0042×X1+0.60 It is characterized by: Effect of the Invention
[0011] According to the present disclosure, it is possible to provide an electrophotographic apparatus and a process cartridge that can provide stable cleaning performance even during endurance use and can prevent the occurrence of starting streaks in the latter half of endurance use under a high-temperature, high-humidity environment. [Brief description of the drawings]
[0012] [Figure 1] FIG. 2 is a schematic perspective view of an example of a cleaning blade; [Diagram 2] Schematic cross-sectional view of a state in which the edge of a cleaning blade is in contact with the surface of an electrophotographic photoreceptor. [Diagram 3] A diagram showing a first line segment that is 10 μm away from the leading edge. [Figure 4] A diagram showing points (1 / 10)L, (5 / 10)L, and (9 / 10)L on a first line segment from one end of the first line segment. [Diagram 5] Diagram showing the locations of P1, P5 and P9 [Figure 6] Diagram showing the position for measuring Martens hardness HM2 [Figure 7] Diagram showing the boundaries of the diffusion index [Figure 8] Schematic diagram showing an example of a mixing treatment device. [Figure 9] FIG. 1 is a schematic diagram showing an example of a configuration of a stirring member; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, a preferred embodiment of the present disclosure will be described with reference to the drawings, but the present disclosure is not limited to the following aspects. In addition, in this disclosure, the description of "XX or more and YY or less" or "XX to YY" representing a numerical range means a numerical range including a lower limit and an upper limit, which are the endpoints, unless otherwise specified. Furthermore, when a numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined. Furthermore, in the following description, configurations having the same function are given the same numbers in the drawings, and their description may be omitted.
[0014] The present disclosure relates to an electrophotographic photoreceptor having a support and a photosensitive layer on the support; a charging means for charging the surface of the electrophotographic photoreceptor; an exposure means for forming a latent image on the surface of the electrophotographic photoreceptor by irradiating the surface of the electrophotographic photoreceptor with exposure light; a developing means having a toner and for developing the latent image with the toner to form a toner image on the surface of the electrophotographic photoreceptor; a transfer means for transferring the toner image onto a transfer material; and Cleaning blade In an electrophotographic apparatus having The cleaning blade is An elastic member including polyurethane; A support member that supports the elastic member; Equipped with the cleaning blade is disposed so that a part of the elastic member is in contact with the surface of the electrophotographic photoreceptor, When the side of the cleaning blade that contacts the surface of the electrophotographic photoreceptor is defined as the tip side of the cleaning blade, The elastic member has at least the tip side, a main surface facing the surface of the electrophotographic photoreceptor; a tip surface which forms a tip edge together with the main surface; The plate shape has Assuming that a first line segment is drawn on the tip surface in parallel to the tip edge, at a distance of 10 μm from the tip edge, and of the same length as the tip edge, The length of the first line segment is L, On the first line segment, The point (1 / 10)L from one end of the first line segment is called P1. The point (2 / 10)L from one end of the first line segment is called P2. The point (3 / 10)L from one end of the first line segment is called P3. A point (4 / 10)L from one end of the first line segment is called P4. The point (5 / 10)L from one end of the first line segment is P5. The point (6 / 10)L from one end of the first line segment is P6. The point (7 / 10)L from one end of the first line segment is P7. The point (8 / 10)L from one end of the first line segment is P8. When the point P9 is (9 / 10)L from one end of the first line segment, When a total of 630 points are taken on the first line segment with a pitch of 1 μm, with each of the points P1 to P9 being the center, and the elastic modulus is measured at each of the 630 points using a scanning probe microscope, the average value of the elastic modulus is 15 MPa or more and 470 MPa or less, and The coefficient of variation of the elastic modulus is 7.0% or less, The Martens hardness of the elastic member measured at the position P5 is defined as HM1, Assuming that a bisector of an angle between the main surface and the tip surface is drawn on a cross section of the elastic member that is perpendicular to the tip surface and the tip edge including P5, the Martens hardness of the elastic member measured at a position on the bisector that is 500 μm away from the tip edge is HM2, |HM1-HM2| is 0.30N / mm 2 is as follows: The toner contains toner particles and an external additive, The number average particle size of the primary particles of the external additive is 5 nm or more and 25 nm or less, a coverage rate X1 of the surface of the toner particles by the external additive as measured by an X-ray photoelectron spectrometer is 50 area % or more and 85 area % or less; When the theoretical coverage rate of the surface of the toner particle by the external additive is X2, the diffusion index represented by the following formula (1) satisfies the following formula (2): (1) Diffusion index = X1 / X2 (2) Diffusion index ≧-0.0042×X1+0.60 The present invention relates to an electrophotographic apparatus characterized in that
[0015] The present disclosure also provides an electrophotographic photoreceptor having a support and a photosensitive layer on the support; a developing means having a toner and for forming a toner image on the surface of the electrophotographic photoreceptor by developing a latent image formed on the surface of the electrophotographic photoreceptor with the toner; and Cleaning blade A process cartridge which is detachably mountable to a main body of an electrophotographic apparatus, The cleaning blade is An elastic member including polyurethane; A support member that supports the elastic member; Equipped with the cleaning blade is disposed so that a part of the elastic member is in contact with the surface of the electrophotographic photoreceptor, When the side of the cleaning blade that contacts the surface of the electrophotographic photoreceptor is defined as the tip side of the cleaning blade, The elastic member has at least the tip side, a main surface facing the surface of the electrophotographic photoreceptor; a tip surface which forms a tip edge together with the main surface; The plate shape has Assuming that a first line segment is drawn on the tip surface in parallel to the tip edge, at a distance of 10 μm from the tip edge, and of the same length as the tip edge, The length of the first line segment is L, On the first line segment, The point (1 / 10)L from one end of the first line segment is called P1. The point (2 / 10)L from one end of the first line segment is called P2. The point (3 / 10)L from one end of the first line segment is called P3. A point (4 / 10)L from one end of the first line segment is called P4. The point (5 / 10)L from one end of the first line segment is P5. The point (6 / 10)L from one end of the first line segment is P6. The point (7 / 10)L from one end of the first line segment is P7. The point (8 / 10)L from one end of the first line segment is P8. When the point P9 is (9 / 10)L from one end of the first line segment, When a total of 630 points are taken on the first line segment with a pitch of 1 μm, with each of the points P1 to P9 being the center, and the elastic modulus is measured at each of the 630 points using a scanning probe microscope, the average value of the elastic modulus is 15 MPa or more and 470 MPa or less, and The coefficient of variation of the elastic modulus is 7.0% or less, The Martens hardness of the elastic member measured at the position P5 is defined as HM1, Assuming that a bisector of an angle between the main surface and the tip surface is drawn on a cross section of the elastic member that is perpendicular to the tip surface and the tip edge including P5, the Martens hardness of the elastic member measured at a position on the bisector that is 500 μm away from the tip edge is HM2, |HM1-HM2| is 0.30N / mm 2 is as follows: The toner contains toner particles and an external additive, The number average particle size of the primary particles of the external additive is 5 nm or more and 25 nm or less, a coverage rate X1 of the surface of the toner particles by the external additive as measured by an X-ray photoelectron spectrometer is 50 area % or more and 85 area % or less; When the theoretical coverage rate of the surface of the toner particle by the external additive is X2, the diffusion index represented by the following formula (1) satisfies the following formula (2): (1) Diffusion index = X1 / X2 (2) Diffusion index ≧-0.0042×X1+0.60 The present invention relates to a process cartridge.
[0016] The cleaning blade includes an elastic member containing polyurethane and a support member that supports the elastic member, and is disposed so that a part of the elastic member abuts against the surface of the electrophotographic photoreceptor. By disposing the cleaning blade in this manner, the cleaning blade cleans the surface of the electrophotographic photoreceptor. Hereinafter, the part of the elastic member that abuts against the surface of the electrophotographic photoreceptor may be referred to as the "abutment portion." When the side of the cleaning blade that comes into contact with the surface of the member to be cleaned is defined as the tip side of the cleaning blade, The elastic member has a plate shape having, at least on the tip side, a main surface facing the electrophotographic photosensitive member and a tip surface forming a tip edge together with the main surface.
[0017] <Cleaning blade configuration> 1 is a schematic perspective view of an example of a cleaning blade. The cleaning blade 1 includes an elastic member 2 and a support member 3 that supports the elastic member 2. 2 is a schematic cross-sectional view of a state in which the edge of the cleaning blade 1 is in contact with the surface of the electrophotographic photoreceptor 6. The elastic member 2 has a main surface 4 facing the surface of the electrophotographic photoreceptor 6, and a tip surface 5 forming a tip edge together with the main surface 4. R indicates the rotation direction of the electrophotographic photoreceptor 6.
[0018] The inventors have found that by configuring the cleaning blade as described below, the cleaning performance is improved over a long period of time even in a high-temperature and high-humidity environment. It is assumed that a first line segment 31 is drawn on the tip surface 5 of the elastic member in parallel with the tip edge, at a distance of 10 μm from the tip edge and of the same length as the tip edge. The length of the first line segment 31 is L, and a point on the first line segment 31 that is (1 / 10)L from one end of the first line segment 31 (the tip surface 5) is P1, a point that is (2 / 10)L from one end of the first line segment 31 is P2, a point that is (3 / 10)L from one end of the first line segment 31 is P3, a point that is (4 / 10)L from one end of the first line segment 31 is P4, The point (5 / 10)L from one end of the first line segment 31 is designated as P5, the point (6 / 10)L from one end of the first line segment 31 is designated as P6, the point (7 / 10)L from one end of the first line segment 31 is designated as P7, the point (8 / 10)L from one end of the first line segment 31 is designated as P8, and the point (9 / 10)L from one end of the first line segment 31 is designated as P9 (see Figures 3, 4, and 5).
[0019] When a total of 630 points, 70 points at a pitch of 1 μm, are taken on the first line segment 31 with each of P1 to P9 as the center, the average elastic modulus value obtained when measuring each of the 630 points using a scanning probe microscope (hereinafter simply referred to as SPM) is 15 MPa or more and 470 MPa or less. If the average value of the elastic modulus is 15 MPa or more, the contact pressure required for cleaning can be obtained, and if it is 470 MPa or less, the toner does not become too hard and has good conformability to an image carrier such as a photoreceptor, thereby preventing the occurrence of cleaning defects. When the number of sheets used increases, the surface of the image carrier such as a photoconductor is scraped by the contact member in the presence of toner containing fine particles, resulting in stripe-like unevenness in the circumferential direction. Therefore, poor followability is likely to cause cleaning defects, but if the elastic modulus is 470 MPa or less, the surface of the image carrier such as a photoconductor can follow even when it has stripe-like unevenness, so that the occurrence of cleaning defects can be suppressed. The average value of the elastic modulus is preferably 15 MPa or more and 460 MPa or less, and more preferably 15 MPa or more and 70 MPa or less. The average value of the elastic modulus can be adjusted by changing the composition of the prepolymer or hardener constituting the polyurethane contained in the elastic member, or by subjecting the elastic member to a surface treatment as described below.
[0020] The coefficient of variation of the elastic modulus of the elastic member is 7.0% or less, preferably 6.0% or less, and more preferably 5.0% or less. The lower limit of the coefficient of variation is not particularly limited. The coefficient of variation is calculated by the following formula: Coefficient of variation = standard deviation of elastic modulus / average elastic modulus x 100 The coefficient of variation is an index showing the degree of aggregation or bias of the hard segment in the elastic member. In the present disclosure, it is necessary that the coefficient of variation is 7.0% or less, that is, the hard segment is uniformly present with little aggregation or bias. When the coefficient of variation is 7.0% or less, not only can the occurrence of cleaning defects be suppressed by applying a uniform force to the contact portion with the photoreceptor, but also the toner present between the elastic member and the photoreceptor can be uniformly applied with few parts that apply a strong force locally. The coefficient of variation can be adjusted by changing the composition of the prepolymer or hardener that constitutes the polyurethane contained in the elastic member, or by subjecting the elastic member to a surface treatment as described below.
[0021] However, when the aggregation of the hard segments is promoted, the hard segments become larger, and there are places where the hard segments are concentrated. As a result, the elastic member may locally apply strong force to the contact portion with the photoconductor and to the toner present between the elastic member and the photoconductor. In that case, the external additive such as silica is released from the toner surface, and a toner having many parts not covered with the external additive is generated, which causes starting streaks caused by the toner melting to the photoconductor. As the aggregation of the hard segments progresses, the separation of the hard segments and the soft segments progresses at the same time. When the elastic modulus of the cleaning blade in this state is measured at 70 points at 1 μm pitch using an SPM, the individual values of the hard segments and the soft segments are detected, and even if the average value of the elastic modulus falls within the above range, the coefficient of variation of the elastic modulus becomes large. In other words, when the coefficient of variation is greater than 7.0%, there are places where the hard segments with advanced aggregation are unevenly distributed, which locally applies strong force to the toner, and starting streaks are generated by the toner melting to the photoconductor.
[0022] In addition, even if the amount of hard segments is reduced and the soft segment portion is increased to make the coefficient of variation 7.0% or less, if the modulus of elasticity is less than 15 MPa, the contact pressure is not applied sufficiently, and the toner may slip through, resulting in streaky image defects. Compared to this state, the cleaning blade according to the present disclosure suppresses the aggregation of hard segments, disperses them finely, and the dispersion is uniform without bias. Therefore, when the modulus of elasticity is measured using an SPM with a small contact area of the probe, the variation between the measured values is also small. Therefore, when the modulus of elasticity is measured at 70 points (9 points x 70 points, a total of 630 points) at 1 μm pitch for each of the above points P1 to P9, the average value of the modulus of elasticity is 15 MPa to 470 MPa, and the coefficient of variation is 7.0% or less.
[0023] When the entire elastic member is in such a finely dispersed state of the hard segments, there are few areas where excessive force is applied to the photoconductor or toner, and force can be applied uniformly, thereby suppressing the occurrence of start-up streaks caused by toner melting to the photoconductor. In particular, in a high-temperature environment, due to the temperature characteristics of the urethane elastomer, the viscosity decreases and the contact pressure tends to increase, so that if the aggregated hard segments are unevenly distributed and there are areas where force is applied locally, toner melting to the photoconductor is likely to occur. The cleaning blade according to the present disclosure can suppress toner melting to the photoconductor, and therefore can suppress the occurrence of start-up streaks in a high-temperature environment.
[0024] By introducing a structure with low regularity or low crystallinity into the hard segment, the aggregation of the hard segment can be suppressed. In addition, if the crystallinity of the soft segment is high, the soft segment tends to gather together, and as a result, the hard segment becomes difficult to disperse. Therefore, by introducing a structure with low crystallinity into the soft segment, the aggregation of the hard segment can be suppressed.
[0025] Furthermore, assuming that a first line segment is drawn on the tip surface of the elastic member parallel to the tip edge, at a distance of 10 μm from the tip edge and of the same length as the tip edge, the length of the first line segment is L, and the Martens hardness of the elastic member measured at a point on the first line segment that is (5 / 10)L from one end of the first line segment (the position P5) is HM1. In addition, assuming that a bisector of the angle between the main surface 4 and the tip surface 5 is drawn on a cross section of the elastic member perpendicular to the tip surface 5 and the tip edge including P5, the Martens hardness of the elastic member measured at a position on the bisector that is 500 μm away from the tip edge is defined as HM2 (see FIG. 6). In the elastic member of the present disclosure, the absolute value of the difference between HM1 and HM2 (the value of |HM1-HM2|) is 0.30 N / mm 2 The absolute value is 0.10 N / mm 2 It is preferable that the resistance is less than 0.05 N / mm 2 The lower limit of the absolute value is not particularly limited, but is, for example, 0.00 N / mm 2 That's all.
[0026] Surface treatment of the elastic member is also useful as a means for making the surface hardness uniform. It is important that the difference in hardness between the inside and the surface of the elastic member is small, and that the hardness is uniform from the surface to the inside. In other words, the absolute value of the difference between HM1 and HM2 (|HM1-HM2|) is 0.30N / mm 2 If the value of |HM1-HM2| is less than 0.30 N / mm, the number of areas that apply a strong local force to the photoconductor or toner is reduced, and the occurrence of starting streaks caused by toner melting onto the photoconductor can be suppressed. 2 If it exceeds this value, the difference in hardness between the surface and the interior of the elastic member becomes large, making the layer with higher hardness at the boundary more likely to chip, resulting in durability issues.
[0027] [Support member] The material constituting the support member of the cleaning blade is not particularly limited, and examples thereof include the following materials: metal materials such as steel plate, stainless steel plate, zinc-plated steel plate, and chrome-free steel plate, and resin materials such as 6-nylon and 6,6-nylon. The structure of the support member is also not particularly limited. It is preferable that one end of the elastic member of the cleaning blade is supported by the support member, as shown in FIG. 2 etc.
[0028] [Elastic member] The polyurethane contained in the elastic member is preferably a polyurethane elastomer. The polyurethane elastomer is obtained mainly from raw materials such as polyol, chain extender, polyisocyanate, catalyst, and other additives. The polyurethane elastomer is a block copolymer consisting of a hard segment and a soft segment. The hard segment is generally composed of a chain extender containing a polyisocyanate and a short-chain diol. On the other hand, the soft segment is generally composed of a long-chain polyol such as polyester polyol, polyether polyol, or polycarbonate polyol, and a polyisocyanate. The content of polyurethane in the elastic member is preferably 90% by mass to 100% by mass.
[0029] Examples of the polyol include the following: polyester polyols such as polyethylene adipate polyol, polybutylene adipate polyol, polyhexylene adipate polyol, (polyethylene / polypropylene) adipate polyol, (polyethylene / polybutylene) adipate polyol, and (polyethylene / polyneopentylene) adipate polyol; polycaprolactone-based polyols obtained by ring-opening polymerization of caprolactone; polyether polyols such as polyethylene glycol, polypropylene glycol, and polytetramethylene glycol; and polycarbonate diols. These may be used alone or in combination of two or more.
[0030] Among the above polyols, polyester polyols using adipate are preferred because they can give polyurethane elastomers with excellent mechanical properties. In particular, polybutylene adipate is preferred. It is more preferable to use a glycol having 4 or more carbon atoms, such as polybutylene adipate polyol or polyhexylene adipate polyol. It is also preferable to use polyols having different glycol carbon numbers, such as polybutylene adipate polyol and polyhexylene adipate polyol. The presence of different types of polyols can further suppress the crystallization of the soft segment and further suppress the aggregation of the hard segment.
[0031] As the chain extender, glycols capable of extending the polyurethane elastomer chain and polyhydric alcohols having three or more functional groups can also be used. Examples of glycols include the following: ethylene glycol (EG), diethylene glycol (DEG), propylene glycol (PG), dipropylene glycol (DPG), 1,4-butanediol (1,4-BD), 1,6-hexanediol (1,6-HD), 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, xylylene glycol (terephthalyl alcohol), and triethylene glycol. These can be used alone or in combination of two or more.
[0032] Examples of trifunctional or higher polyhydric alcohols include trimethylolpropane, glycerin, pentaerythritol, and sorbitol. These may be used alone or in combination of two or more.
[0033] One method for improving the elastic modulus of polyurethane elastomers is to introduce crosslinking. As a method for introducing crosslinking, it is preferable to use a polyhydric alcohol having three or more functional groups as the chain extender. In addition, if there are too many branches, it is difficult to react all the hydroxyl groups, and it is difficult to obtain the intended degree of crosslinking. Therefore, it is more preferable to use a trifunctional alcohol among the polyhydric alcohols. Among them, trimethylolpropane (TMP) is more preferable because it has a methylene skeleton next to the hydroxyl group, which allows a flexible crosslinking structure in terms of molecular structure and has the effect of suppressing the crystallinity of the hard segment.
[0034] The concentration of the trifunctional alcohol calculated by the following formula (3) is preferably 0.22 mmol / g to 0.39 mmol / g. If it is 0.22 mmol / g or more, it is very effective in suppressing hard segment aggregation, and edge chipping of the cleaning blade can be further suppressed. If it is 0.39 mmol / g or less, the elastic modulus due to the introduction of crosslinks does not become too high, so that the conformability to the image carrier is very good, and the occurrence of cleaning defects can be further suppressed.
number
[0035] Examples of the polyisocyanate include the following: 4,4'-diphenylmethane diisocyanate (4,4'-MDI), polymeric MDI, 2,4-tolylene diisocyanate (2,4-TDI), 2,6-tolylene diisocyanate (2,6-TDI), xylene diisocyanate (XDI), 1,5-naphthylene diisocyanate (1,5-NDI), p-phenylene diisocyanate (PPDI), hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), 4,4'-dicyclohexylmethane diisocyanate (hydrogenated MDI), tetramethylxylene diisocyanate (TMXDI), and carbodiimide-modified MDI. Among these, 4,4'-MDI is preferred because the two isocyanate groups have the same reactivity and high mechanical properties can be obtained. In addition, since the polyisocyanate that forms the hard segment itself has a branched structure, it is more preferable to use polymeric MDI in combination, which has a very high effect of suppressing the aggregation of the hard segment.
[0036] As the catalyst, a catalyst generally used for curing polyurethane elastomers can be used. Examples of the catalyst include tertiary amine catalysts, and specific examples thereof include the following: amino alcohols such as dimethylethanolamine, N,N,N'-trimethylaminopropylethanolamine, and N,N'-dimethylhexanolamine; trialkylamines such as triethylamine; tetraalkyldiamines such as N,N,N'N'-tetramethyl-1,3-butanediamine; triethylenediamine, piperazine compounds, and triazine compounds. In addition, organic acid salts of metals such as potassium acetate and potassium alkali octylate can also be used. Furthermore, metal catalysts generally used in urethanization, such as dibutyltin dilaurate, can also be used. These can be used alone or in combination of two or more.
[0037] The raw materials constituting the elastic member may contain additives such as pigments, plasticizers, waterproofing agents, antioxidants, ultraviolet absorbing agents, and light stabilizers, if necessary.
[0038] [Manufacturing method of cleaning blade] The method for producing a cleaning blade is not particularly limited, and an appropriate method may be selected from among known methods. For example, after placing a support member in a mold for a cleaning blade, the polyurethane raw material composition is injected into the cavity and heated to harden, thereby obtaining a cleaning blade in which a plate-shaped blade member and a support member are integrated. Alternatively, a polyurethane elastomer sheet is separately molded from the polyurethane raw material composition, and cut into strips to prepare an elastic member, and the adhesive portion of the elastic member is superimposed on a support member to which an adhesive has been applied or attached, and the adhesive is adhered by heating and pressurizing.
[0039] By carrying out the surface treatment, the elastic modulus measured by SPM at the tip surface of the cleaning blade can be increased. The light source used in the surface treatment process generates ultraviolet light. In particular, it is preferable that the wavelength of the maximum emission peak is in the vicinity of 254 nm, for example, in the range of 254±1 nm. This is because ultraviolet light in the above wavelength range or with the above wavelength can efficiently generate active oxygen that modifies the polyurethane surface. When there are multiple ultraviolet emission peaks, it is preferable that one of them is in the vicinity of 254 nm.
[0040] The intensity of the light emitted from the light source is not particularly limited, and values measured using a spectroradiometer (USR-40V / D, manufactured by Ushio Inc.), an ultraviolet ray integrating light meter (UIT-150-A, UVD-S254, VUV-S172, VUV-S365, manufactured by Ushio Inc.), or the like can be used. The integrated amount of ultraviolet light irradiated onto the polyurethane in the surface treatment step may be appropriately selected depending on the effect of the surface treatment to be obtained. This can be determined by the irradiation time of light from the light source, the output of the light source, the distance from the light source, and the like, and may be, for example, 10,000 mJ / cm. 2 etc., may be determined so as to obtain a desired integrated light quantity. The integrated amount of ultraviolet light irradiated onto the conductive member can be calculated by the following method. UV light intensity (mJ / cm2 ) = UV intensity (mW / cm 2 ) x irradiation time (sec) As a light source that emits ultraviolet light, for example, a high pressure mercury lamp or a low pressure mercury lamp can be suitably used. These light sources are preferable because they can stably emit ultraviolet light of a suitable wavelength that is less attenuated depending on the irradiation distance, and can easily irradiate the entire surface uniformly.
[0041] <Process cartridge and electrophotographic apparatus> The cleaning blade can be used by being incorporated in a process cartridge that is detachably attached to the main body of an electrophotographic apparatus. The process cartridge includes, for example, an electrophotographic photoreceptor having a support and a photosensitive layer on the support, and a toner. and a developing means for developing a latent image formed on the surface of the electrophotographic photoreceptor with the toner to form a toner image on the surface of the electrophotographic photoreceptor, and a cleaning blade. The above-mentioned cleaning blade can be used in such a process cartridge. The process cartridge may further include a toner container, a toner supply roller, a developing roller, a charging roller, etc. Such a process cartridge contributes to the stable formation of high-quality electrophotographs.
[0042] The electrophotographic apparatus includes an electrophotographic photoreceptor having a support and a photosensitive layer on the support, a charging means for charging the surface of the electrophotographic photoreceptor, an exposure means for forming a latent image on the surface of the electrophotographic photoreceptor by irradiating the surface of the electrophotographic photoreceptor with exposure light, a developing means having a toner and developing the latent image with the toner to form a toner image on the surface of the electrophotographic photoreceptor, a transfer means for transferring the toner image to a transfer material, and a cleaning blade, and the above-mentioned cleaning blade can be used in such an electrophotographic apparatus. Such an electrophotographic apparatus can stably form high-quality electrophotographic images.
[0043] <Toner> In the present disclosure, in addition to the above-mentioned improvement of the cleaning blade, it is necessary to make the amount of external additive present as aggregates on the toner particle surface small and the amount present as primary particles large. Even if the cleaning blade of the present disclosure applies a uniform force to the toner and suppresses the separation of external additives such as silica fine particles from the toner particle surface, when the external additives on the toner particle surface are in an aggregated state, there are many parts that are not covered with the external additives, which leads to the occurrence of starting streaks due to drum fusion. In addition, when the external additives exist as aggregates on the toner surface, when the aggregates move to the photoconductor, the toner may fuse from the aggregates, which may lead to the occurrence of starting streaks. Therefore, in the present disclosure, in order to prevent the occurrence of starting streaks caused by toner fusing to the drum, it is necessary to improve both the cleaning blade of the present disclosure and to increase the amount of external additives present as primary particles on the surface of the toner particles.
[0044] The number average particle diameter of the primary particles of the external additive is 5 nm or more and 25 nm or less. If the number average particle diameter is smaller than 5 nm, the Van der Waals force between the external additives is too strong, causing electrostatic aggregation between the external additives, and the external additives are easily detached from the surface of the toner particles. If the number average particle diameter is larger than 25 nm, the Van der Waals force between the toner particle surface and the external additive is reduced, and the external additive is easily detached from the surface of the toner particles. The number average particle diameter is preferably 6 nm to 20 nm, more preferably 6 nm to 17 nm.
[0045] In addition, the coverage rate X1 of the surface of the toner particles by the external additives measured by an X-ray photoelectron spectroscopy (hereinafter also referred to as ESCA) is 50 area % or more and 85 area % or less. If it is within this range, it is possible to create a state in which the external additives are close to each other and are difficult to separate from the toner particle surface due to the interaction due to Van der Waals forces. In order to keep the coverage rate X1 within the above range, a method of controlling the mixing conditions of the external additives can be mentioned. When the coverage rate X1 is less than 50 area%, the distance between the external additives is too far, the interaction due to Van der Waals force does not work sufficiently, the external additives cannot be sufficiently prevented from being separated from the toner particle surface, and the occurrence of start-up streaks cannot be suppressed. When the coverage rate is more than 85 area%, while it is possible to create a state in which the external additives are difficult to separate, it may not be possible to suppress the occurrence of start-up streaks in a high-temperature and high-humidity environment, or the cleaning ability may be reduced during durability testing. The coverage rate X1 is preferably 50 area% or more and 80 area% or less, more preferably 60 area% or more and 80 area% or less.
[0046] Furthermore, when the theoretical coverage of the surface of the toner particle by the external additive is taken as X2, the diffusion index represented by the following formula (1) satisfies the following formula (2). (1) Diffusion index = X1 / X2 (2) Diffusion index ≧-0.0042×X1+0.60 The coverage rate X1 is calculated as follows. (i) Calculate the detection intensity Xa of the characteristic atoms that constitute the external additive when the external additive alone is measured by ESCA. (ii) Next, the toner sample is measured by ESCA to determine the detection intensity Xb of the atoms originating from the external additive (the same atoms as in (i)). The coverage rate X1 is calculated from the ratio of Xb to Xa (Xb / Xa). For example, when silica fine particles are used as an external additive, it can be calculated from the ratio of the detection intensity of Si atoms when the toner is measured to the detection intensity of Si atoms when the silica fine particles alone are measured by ESCA. When a plurality of types of external additives are used, the above-mentioned coverage rate X1 is determined for each external additive, and the total value of these coverage rates is taken as X1. This coverage rate X1 indicates the ratio of the area of the toner particle surface that is actually covered with the external additive.
[0047] On the other hand, the theoretical coverage rate X2 by the external additive is calculated from the mass parts of the external additive per 100 mass parts of toner particles, the particle size of the external additive, etc., using the following formula (4). This indicates the proportion of the area that can theoretically cover the surface of the toner particles. (4) Theoretical coverage X2 (area %)= 3 1 / 2 / (2π)×(dt / da)×(ρt / ρa)×C×100 When multiple types of external additives are used, the theoretical coverage rate X2 is calculated for each external additive, and these values are added together to form X2. da: Number average particle diameter of external additive (D1) dt: weight average particle size of toner (D4) ρa: True density of external additive ρt: True density of toner C: Mass of external additive / Mass of toner (=Number of parts of external additive added to 100 parts by mass of toner particles (parts by mass) / (Number of parts of external additive added to 100 parts by mass of toner particles (parts by mass) + 100 (parts by mass)) In addition, when the amount of external additive added is unknown, the amount of external additive added is calculated based on the measurement method of "Content of external additive in toner" described later and used as "C". In addition, the number average particle diameter (D1) of the external additive is a value obtained based on the measurement method of the number average particle diameter (D1) of the primary particles of the external additive based on the surface observation of the toner particles described later. However, when multiple types of external additives are used, etc., and calculation by the surface observation method is difficult, the number average particle diameter of each external additive measured in advance may be used.
[0048] The physical meaning of the diffusion exponent expressed by the above formula (1) is given below. The diffusion index indicates the deviation between the measured coverage rate X1 and the theoretical coverage rate X2. The degree of this deviation is considered to indicate the amount of external additive layered in two or three layers in the vertical direction from the surface of the toner particle. Ideally, the diffusion index is 1, which is the case when the coverage rate X1 is equal to the theoretical coverage rate X2, and there is no external additive layered in two or more layers. On the other hand, if the external additive is present on the toner surface as an aggregate, the measured coverage rate will deviate from the theoretical coverage rate, and the diffusion index will be low. In other words, the diffusion index can be said to indicate the amount of the external additive present as an aggregate.
[0049] The diffusion index is preferably in the range shown in the above formula (2). Indicates that it is preferable for a number to be equal to or greater than a certain value. A large diffusion index indicates that the amount of the external additive present on the surface of the toner particles as aggregates is small, and the amount present as primary particles is large. When the external additive exists as primary particles, the external additive can be fixed to the surface of the toner particles in a more uniform state. Therefore, the occurrence of start-up streaks in a high-temperature and high-humidity environment can be suppressed.
[0050] The boundary line of the diffusion index is a function with the coverage rate X1 as a variable in the range of coverage rate X1 from 50 area % to 85 area %. This function was calculated by producing toners with different coverage rates X1 by varying the amount of external additives added using three types of external additive mixing conditions, and creating a graph (FIG. 7) that plots the relationship between coverage rate X1 and diffusion index. The toners plotted on this graph were evaluated for start-up streaks and cleaning performance during durability in a high-temperature, high-humidity environment using the cleaning blade of the present disclosure. As a result, it was found that for toners plotted in the region satisfying formula (2), the use of the cleaning blade of the present disclosure can suppress the occurrence of start-up streaks in a high-temperature, high-humidity environment, and stable cleaning performance can be obtained even during durability.
[0051] Here, the inventors speculate as follows about the reason why the diffusion index depends on the coverage rate X1. To suppress the occurrence of start-up streaks, it is better to have a small amount of external additive present as secondary particles, but the coverage rate X1 also has a significant effect. As the coverage rate X1 increases, the effect of suppressing start-up streaks gradually improves, so the allowable amount of external additive present as secondary particles increases. In this way, it is believed that the boundary line of the diffusion index is a function with the coverage rate X1 as a variable. That is, there is a correlation between the coverage rate X1 and the diffusion index, and it is preferable to control the diffusion index in accordance with the coverage rate X1.
[0052] The theoretical coverage X2 is preferably 80 area % to 350 area %, and more preferably 100 area % to 200 area %. Specifically, the diffusion index is preferably 0.51 to 0.56. Furthermore, the value of -0.0042 x X1 + 0.60 is preferably 0.25 to 0.35.
[0053] The adhesion rate F of the external additive to the toner particles is preferably 75% or more. In the above range, when the toner is subjected to a force between the cleaning blade and the photoconductor, the external additive is less likely to be detached from the toner particle surface, and the occurrence of starting streaks caused by the toner melting to the photoconductor can be further suppressed. The adhesion rate F is more preferably 80% or more. The upper limit of the adhesion rate F is not particularly limited, but is, for example, 100% or less.
[0054] The external additive preferably contains a hydrotalcite compound. By including a hydrotalcite compound in the external additive, it is possible to further prevent the detachment of other external additives from the surfaces of the toner particles, and to further suppress the occurrence of starting streaks. This effect can be obtained regardless of the type of external additive or the chargeability of the toner, but is preferably obtained when the external additive further includes silica fine particles or when the toner is a negatively chargeable toner. The present inventors consider the reason for this to be as follows: In the case of a negatively charged toner, the hydrotalcite compound often has a more positive polarity than the toner particles and the silica fine particles, and the hydrotalcite compound exerts an adhesive force on both the toner particles and the silica fine particles. Therefore, it is considered that the presence of the hydrotalcite compound makes it difficult for the silica fine particles to separate from the toner particles.
[0055] The external additive preferably contains silica fine particles. The silica fine particles may be those obtained by a dry method such as fumed silica, or those obtained by a wet method such as a sol-gel method. From the viewpoint of chargeability, it is preferable to use those obtained by a dry method. stomach. The silica fine particles may be surface-treated to impart hydrophobicity and fluidity. Examples of hydrophobicity include chemical treatment with an organosilicon compound that reacts with or physically adsorbs to the silica fine particles. A preferred method is to treat silica produced by vapor phase oxidation of a silicon halide compound with an organosilicon compound. Examples of such organosilicon compounds include the following.
[0056] Hexamethyldisilazane, trimethylsilane, trimethylchlorosilane, trimethylethoxysilane, dimethyldichlorosilane, methyltrichlorosilane, allyldimethylchlorosilane, allylphenyldichlorosilane, benzyldimethylchlorosilane. Further examples include bromomethyldimethylchlorosilane, α-chloroethyltrichlorosilane, β-chloroethyltrichlorosilane, chloromethyldimethylchlorosilane, triorganosilyl mercaptan, trimethylsilyl mercaptan, and triorganosilyl acrylate. Further examples include vinyldimethylacetoxysilane, dimethylethoxysilane, dimethyldimethoxysilane, diphenyldiethoxysilane, and 1-hexamethyldisiloxane. Further examples include 1,3-divinyltetramethyldisiloxane, 1,3-diphenyltetramethyldisiloxane, and dimethylpolysiloxane having 2 to 12 siloxane units per molecule and having one hydroxyl group on each Si of the units located at the terminals. These may be used alone or in combination of two or more.
[0057] Silicone oil may be used for the surface treatment of the silica fine particles. That is, the silica fine particles may be silicone oil-treated silica fine particles. Examples of the silicone oil used for the surface treatment of the silica fine particles include dimethyl silicone oil, methylphenyl silicone oil, α-methylstyrene-modified silicone oil, chlorophenyl silicone oil, and fluorine-modified silicone oil. Preferred silicone oils include those having a viscosity of 30 mm at 25° C. 2 / s or more 1000mm 2 / s or less is used.
[0058] Examples of the method for surface treatment of silica fine particles with silicone oil include the following method. A method in which silica particles treated with a silane coupling agent are directly mixed with silicone oil using a mixer such as a Henschel Mixer (product name). A method of spraying silicone oil onto silica fine particles as a base, or a method of dissolving or dispersing silicone oil in a suitable solvent, adding silica fine particles and mixing, and then removing the solvent. It is more preferable that, after the silicone oil treatment, the silica particles are heated in an inert gas to a temperature of 200° C. or higher (more preferably 250° C. or higher) to stabilize the surface coat. The silane coupling agent is not particularly limited, but preferably includes hexamethyldisilazane (HMDS).
[0059] In order to improve the performance of the toner, the toner may further contain other external additives. The other external additives may include known inorganic fine particles, known organic fine particles, and known organic-inorganic composite fine particles composed of inorganic and organic substances. Examples of inorganic fine particles other than silica fine particles and hydrosalcite compounds include alumina fine particles, titania fine particles, and composite oxide fine particles thereof. The content of the external additive is preferably 0.05 parts by mass to 5.0 parts by mass with respect to 100 parts by mass of the toner particles. In addition, the ratio of the external additive other than the hydrotalcite compound (for example, silica fine particles) to the hydrotalcite compound in the external additive is preferably 10% by mass to 20% by mass. It is preferably expressed as % by mass.
[0060] A preferred method for adding an external additive to toner particles will be described. As a mixing and processing device for externally mixing the external additive, a known mixing and processing device can be used, but a device such as that shown in Figure 8 is preferred in that it can easily control the coverage rate X1 or the diffusion index.
[0061] FIG. 8 is a schematic diagram showing an example of a mixing processing device that can be used when externally mixing an external additive. The mixing and processing device is configured such that a shear is applied to the toner particles and the external additives in a narrow clearance area, so that the external additives can be attached to the surfaces of the toner particles while being broken down from secondary particles to primary particles. Furthermore, as described later, the toner particles and the external additives tend to circulate in the axial direction of the rotating body and tend to be sufficiently uniformly mixed before adhesion progresses, which makes it easy to control the coverage rate X1 or the diffusion index within the range required in the present disclosure. 9 is a schematic diagram showing an example of the configuration of a stirring member used in the above-mentioned mixing processing device. The external addition mixing step of the external additive will be described below with reference to FIGS.
[0062] The mixing processing device for externally mixing the above-mentioned external additives has a rotor 19 having at least a plurality of stirring members 20 installed on its surface, a drive unit 8 for rotating the rotor, and a main casing 18 provided with a gap between the stirring members 20. The gap (clearance) between the inner periphery of the main casing 18 and the stirring members 20a, 20b can be kept constant and small to apply a uniform shear to the toner particles, loosening the external additives from secondary particles to primary particles and making it easier for them to adhere to the toner particle surface.
[0063] Furthermore, in this device, the diameter of the inner periphery of the main casing 18 can be set to no more than twice the diameter of the outer periphery of the rotor 19. Fig. 8 shows an example in which the diameter of the inner periphery of the main casing 18 is 1.7 times the diameter of the outer periphery of the rotor 19 (the diameter of the body part of the rotor 19 excluding the stirring member 20). When the diameter of the inner periphery of the main casing 18 is no more than twice the diameter of the outer periphery of the rotor 19, the processing space in which a force acts on the toner particles is appropriately limited, so that a sufficient impact force is applied to the external additive that has become secondary particles.
[0064] The clearance can be adjusted according to the size of the main casing. It is preferable to set the clearance to about 1% to 5% of the diameter of the inner periphery of the main casing 18 in order to apply sufficient shear to the external additive. Specifically, when the diameter of the inner periphery of the main casing 18 is about 130 mm, the clearance is preferably set to about 2 mm to 5 mm, and when the diameter of the inner periphery of the main casing 18 is about 800 mm, the clearance is preferably set to about 10 mm to 30 mm.
[0065] In the external additive mixing process, it is preferable to use a mixing treatment device shown in FIG. 8, rotate a rotor 19 by a drive unit 8, and stir and mix the toner particles and external additives fed into the mixing treatment device, thereby externally mixing the external additives onto the surfaces of the toner particles. As shown in Fig. 9, at least some of the multiple stirring members 20 are formed as feeding stirring members 20a that feed the toner particles and external additives in one axial direction of the rotor 19 as the rotor 19 rotates. At least some of the multiple stirring members 20a, 20b are formed as returning stirring members 20b that return the toner particles and external additives in the other axial direction of the rotor as the rotor 19 rotates. Here, when the raw material inlet 22 and the product outlet 23 are provided at both ends of the main casing 18 as shown in Fig. 8, the direction from the raw material inlet 22 to the product outlet 23 (the rightward direction in Fig. 8) is referred to as the "feed direction". That is, as shown in FIG. 9, the plate surface of the stirring member 20a for feeding is inclined so as to feed the toner particles in the feeding direction (13). On the other hand, the plate surface of the stirring member 20b is inclined so as to feed the toner particles in the return direction (12). The toner particles and external additives are fed through the nozzle.
[0066] This allows the external additive to be mixed on the surface of the toner particles while repeatedly feeding in the "feed direction" (13) and feeding in the "return direction" (12). The stirring members 20a and 20b are each a set of multiple members spaced apart in the circumferential direction of the rotor 19. In the example shown in FIG. 9, the stirring members 20a and 20b are each a set of two members spaced 180 degrees apart from each other on the rotor 19, but the stirring members 20a and 20b may be a set of multiple members, such as three members spaced 120 degrees apart or four members spaced 90 degrees apart. In the example shown in FIG. 9, a total of 12 stirring members 20a and 20b are formed at equal intervals. Furthermore, in Fig. 9, D is the width of the agitating members, and d is the distance indicating the overlapping portion of the agitating members. From the viewpoint of efficiently sending toner particles and external additives in the forward and return directions, it is preferable that D is a width of 20% or more and approximately 30% of the length of rotating body 19 in Fig. 9. Fig. 9 shows an example where it is 23%. Furthermore, it is preferable that agitating members 20a and 20b have a certain degree of overlapping portion d between agitating member 20b and agitating member 20a when an extension line is drawn vertically from the end position of agitating member 20a.
[0067] This makes it possible to efficiently apply shear to the external additive in the form of secondary particles. In terms of applying shear, it is preferable that d with respect to D is 10% or more and 30% or less. As for the shape of the blade, other than the shape shown in FIG. 9, as long as it can send toner particles in both the forward and return directions and can maintain clearance, it may have a curved shape or a paddle structure in which the tip of the blade is connected to the rotor 19 by a rod-shaped arm. The device will be described in more detail below with reference to the schematic diagrams of the device shown in Figures 8 and 9. The device shown in Figure 8 has a rotor 19 having at least a plurality of stirring members 20a, 20b mounted on its surface, a drive unit 8 that rotates the rotor 19, a main casing 18 that is provided with a gap between the stirring members 20a, 20b, and a jacket 21 that is located inside the main casing 18 and on the side surface 10 of the rotor end and through which a cooling or heating medium can flow.
[0068] Furthermore, the device shown in FIG. 8 has a raw material inlet 22 formed in the upper part of the main casing 18 for introducing toner particles and external additives, and a product outlet 23 formed in the lower part of the main casing 18 for discharging the toner that has been mixed with the external additives from the main casing 18 to the outside. Furthermore, in the device shown in FIG. 8, an inner piece 16 for a raw material inlet is inserted into the raw material inlet 22, and an inner piece 17 for a product outlet is inserted into the product outlet . First, the inner piece 16 for the raw material inlet is removed from the raw material inlet 22, and toner particles are fed into the processing space 9 through the raw material inlet 22. Next, external additives are fed into the processing space 9 through the raw material inlet 22, and the inner piece 16 for the raw material inlet is inserted. Next, the rotor 19 is rotated by the drive unit 8 (11 indicates the direction of rotation), and the material fed above is stirred and mixed by the stirring members 20a, 20b provided on the surface of the rotor 19, for external addition mixing processing. The order of feeding may be such that the external additives are first fed through the raw material feeding port 22, and then the toner particles are fed through the raw material feeding port 22. Alternatively, the toner particles and the external additives may be mixed in advance with a mixer such as a Henschel Mixer (product name), and then the mixture may be fed through the raw material feeding port 22 of the device shown in FIG.
[0069] More specifically, as an external addition mixing treatment condition, it is preferable to control the power of the driving unit 8 to 0.2 W / g or more and 2.0 W / g or less in order to obtain the coverage X1 and diffusion index specified in the present disclosure. It is more preferable to control the power of the driving unit 8 to 0.6 W / g or more and 1.6 W / g or less. When the power is 0.2 W / g or more, the coverage rate X1 tends to be high and the diffusion index tends to be high. On the other hand, when the power is 2.0 W / g or less, the diffusion index is high and the external additive is embedded. This tends to prevent overcrowding. The treatment time is not particularly limited, but is preferably 3 minutes or more and 10 minutes or less. When the treatment time is 3 minutes or more, the coverage rate X1 and the diffusion index tend to be high. The rotation speed of the stirring member during external addition mixing is not particularly limited, but when the volume of the treatment space 9 of the device shown in FIG. 9 is 2.0×10 -3 m 3 In this device, the rotation speed of the stirring members 20a and 20b when they have the shape shown in Fig. 9 is preferably 800 rpm or more and 3000 rpm or less. By rotating the stirring members 20a and 20b at 800 rpm or more and 3000 rpm or less, the coverage rate X1 and the diffusion index defined in the present disclosure can be easily obtained.
[0070] Furthermore, a particularly preferred processing method is to have a pre-mixing step before the external additive mixing processing operation. By including the pre-mixing step, the external additive is highly uniformly dispersed on the toner particle surface, which tends to increase the coverage rate X1 and also tends to increase the diffusion index. More specifically, the pre-mixing process conditions are preferably such that the power of the drive unit 8 is 0.06 W / g or more and 0.20 W / g or less, and the process time is 0.5 minutes or more and 1.5 minutes or less. When the pre-mixing process conditions are such that the load power is 0.06 W / g or more, or the process time is 0.5 minutes or more, sufficient uniform mixing is likely to be achieved as pre-mixing. On the other hand, when the pre-mixing process conditions are such that the load power is 0.20 W / g or less, or the process time is 1.5 minutes or less, sufficient uniform mixing is achieved and then the external additive is fixed to the toner particle surface.
[0071] Regarding the rotation speed of the stirring member in the pre-mixing process, the volume of the processing space 9 of the device shown in FIG. -3 m 3In this device, the rotation speed of the stirring members 20a and 20b when they have the shape shown in Fig. 9 is preferably 50 rpm or more and 500 rpm or less. By rotating the stirring members 20a and 20b at 50 rpm or more and 500 rpm or less, the coverage rate X1 and the diffusion index defined in the present disclosure can be easily obtained.
[0072] After the external additive mixing process is completed, the inner piece 17 for product discharge is removed from the product discharge port 23, and the rotor 19 is rotated by the drive unit 8 to discharge the toner from the product discharge port 23. If necessary, the obtained toner can be separated into coarse particles using a sieve such as a circular vibration sieve to obtain the toner.
[0073] The method for producing the toner particles will be described. The toner particles can be produced by a known method, for example, a kneading and grinding method or a wet production method. From the viewpoint of uniformity of the particle size and shape controllability, the wet production method is preferably used. Further, examples of the wet production method include a suspension polymerization method, a dissolution suspension method, an emulsion polymerization aggregation method, and an emulsion aggregation method, and the emulsion aggregation method is preferably used.
[0074] An example of a method for producing toner particles using the emulsion aggregation method will be described. In the emulsion aggregation method, first, fine particles of a binder resin and materials such as a colorant as necessary are dispersed and mixed in an aqueous medium containing a dispersion stabilizer. A surfactant may be added to the aqueous medium. Then, an aggregating agent is added to generate associated particles by aggregating them to a desired particle size, and then or simultaneously with the aggregating, the associated particles are fused together. If necessary, the shape is controlled by heat to form toner particles. Here, the fine particles of the binder resin can be composite particles formed of a plurality of layers having a structure of two or more layers containing resins with different compositions. For example, the toner particles can be produced by emulsion polymerization, mini-emulsion polymerization, phase inversion emulsification, or the like, or by combining several production methods.
[0075] When the internal additive is contained in the toner particles, the internal additive may be contained in the resin fine particles, or a dispersion liquid of internal additive fine particles containing the internal additive may be separately prepared, and the internal additive fine particles may be aggregated together with the resin fine particles when the resin fine particles are aggregated. It is also possible to prepare toner particles having layer structures with different compositions by adding the above at different times and aggregating them.
[0076] Examples of the dispersion stabilizer that can be used include the following: Inorganic dispersion stabilizers include tricalcium phosphate, magnesium phosphate, zinc phosphate, aluminum phosphate, calcium carbonate, magnesium carbonate, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, calcium metasilicate, calcium sulfate, barium sulfate, bentonite, silica, and alumina. Examples of the organic dispersion stabilizer include polyvinyl alcohol, gelatin, methyl cellulose, methylhydroxypropyl cellulose, ethyl cellulose, sodium salt of carboxymethyl cellulose, and starch.
[0077] As the surfactant, a known cationic surfactant, anionic surfactant, or nonionic surfactant can be used. Specific examples of the cationic surfactant include dodecyl ammonium bromide, dodecyl trimethyl ammonium bromide, dodecyl pyridinium chloride, dodecyl pyridinium bromide, and hexadecyl trimethyl ammonium bromide. Specific examples of nonionic surfactants include dodecyl polyoxyethylene ether, hexadecyl polyoxyethylene ether, nonylphenyl polyoxyethylene ether, lauryl polyoxyethylene ether, sorbitan monooleate polyoxyethylene ether, styrylphenyl polyoxyethylene ether, and monodecanoyl sucrose. Specific examples of anionic surfactants include aliphatic soaps such as sodium stearate and sodium laurate, sodium lauryl sulfate, sodium dodecylbenzenesulfonate, and sodium polyoxyethylene (2) lauryl ether sulfate.
[0078] The binder resin constituting the toner particles will be described. Preferred examples of the binder resin include vinyl resins and polyester resins. Examples of the vinyl resins, polyester resins and other binder resins include the following resins or polymers. Homopolymers of styrene and its substituted derivatives such as polystyrene and polyvinyltoluene; styrene-based copolymers such as styrene-propylene copolymers, styrene-vinyltoluene copolymers, styrene-vinylnaphthalene copolymers, styrene-methyl acrylate copolymers, styrene-ethyl acrylate copolymers, styrene-butyl acrylate copolymers, styrene-octyl acrylate copolymers, styrene-dimethylaminoethyl acrylate copolymers, styrene-methyl methacrylate copolymers, styrene-ethyl methacrylate copolymers, styrene-butyl methacrylate copolymers, styrene-dimethylaminoethyl methacrylate copolymers, styrene-vinyl methyl ether copolymers, styrene-vinyl ethyl ether copolymers, styrene-vinyl methyl ketone copolymers, styrene-butadiene copolymers, styrene-isoprene copolymers, styrene-maleic acid copolymers, and styrene-maleic acid ester copolymers; polymethyl methacrylate, polybutyl methacrylate, polyvinyl acetate, polyethylene, polypropylene, polyvinyl butyral, silicone resins, polyamide resins, epoxy resins, polyacrylic resins, rosin, modified rosin, terpene resins, phenolic resins, aliphatic or alicyclic hydrocarbon resins, and aromatic petroleum resins. These binder resins can be used alone or in combination of two or more.
[0079] Polymerizable monomers that can be used in the production of vinyl resins include styrene monomers such as styrene and α-methylstyrene; acrylic acid esters such as methyl acrylate and butyl acrylate; methacrylic acid esters such as methyl methacrylate, 2-hydroxyethyl methacrylate, t-butyl methacrylate, and 2-ethylhexyl methacrylate; unsaturated carboxylic acids such as acrylic acid and methacrylic acid; unsaturated dicarboxylic acids such as maleic acid; unsaturated dicarboxylic anhydrides such as maleic anhydride; and nitrile vinyls such as acrylonitrile. monomers; halogen-containing vinyl monomers such as vinyl chloride; nitro vinyl monomers such as nitrostyrene; and the like.
[0080] The binder resin preferably contains a carboxy group, and is preferably a resin produced using a polymerizable monomer containing a carboxy group. Examples of the polymerizable monomer containing a carboxy group include vinyl carboxylic acids such as acrylic acid, methacrylic acid, α-ethylacrylic acid, and crotonic acid; unsaturated dicarboxylic acids such as fumaric acid, maleic acid, citraconic acid, and itaconic acid; and unsaturated dicarboxylic acid monoester derivatives such as succinic acid monoacryloyloxyethyl ester, succinic acid monoacryloyloxyethyl ester, phthalic acid monoacryloyloxyethyl ester, and phthalic acid monomethacryloyloxyethyl ester.
[0081] As the polyester resin, for example, a condensation polymerization product of the following carboxylic acid component and alcohol component can be used. Examples of the carboxylic acid component include terephthalic acid, isophthalic acid, phthalic acid, fumaric acid, maleic acid, cyclohexanedicarboxylic acid, and trimellitic acid. Examples of the alcohol component include bisphenol A, hydrogenated bisphenol, ethylene oxide adduct of bisphenol A, propylene oxide adduct of bisphenol A, glycerin, trimethylolpropane, and pentaerythritol. The polyester resin may be a polyester resin containing a urea group. It is preferable that the carboxyl group at the terminal of the polyester resin is not capped.
[0082] In order to control the molecular weight of the binder resin, a crosslinking agent may be added during polymerization of the polymerizable monomer. Examples of the crosslinking agent include ethylene glycol dimethacrylate, ethylene glycol diacrylate, diethylene glycol dimethacrylate, diethylene glycol diacrylate, triethylene glycol dimethacrylate, triethylene glycol diacrylate, neopentyl glycol dimethacrylate, neopentyl glycol diacrylate, divinylbenzene, bis(4-acryloxypolyethoxyphenyl)propane, ethylene glycol diacrylate, 1,3-butylene glycol diacrylate, 1,4-butanediol diacrylate, 1,5-pentanediol diacrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, polyethylene glycol #200, #400, and #600 diacrylates, dipropylene glycol diacrylate, polypropylene glycol diacrylate, and polyester diacrylate (MANDA Nippon Kayaku), as well as compounds in which the acrylate is replaced with methacrylate. The amount of the crosslinking agent added is preferably 0.001 parts by mass or more and 15,000 parts by mass or less based on 100 parts by mass of the polymerizable monomer.
[0083] The toner particles preferably contain a release agent. The release agent is more preferably an ester wax. It is also more preferable that the melting point of the release agent is 60° C. or more and 90° C. or less. It is even more preferable that the toner particles contain an ester wax having a melting point of 60° C. or more and 90° C. or less. Such wax has excellent compatibility with the binder resin, and therefore a plasticizing effect is easily obtained.
[0084] Examples of ester waxes include waxes mainly composed of fatty acid esters, such as carnauba wax and montan acid ester wax; fatty acid esters from which some or all of the acid components have been deoxidized, such as deoxidized carnauba wax; methyl ester compounds having a hydroxyl group obtained by hydrogenating vegetable oils and fats; saturated fatty acid monoesters, such as stearyl stearate and behenyl behenate; dibehenyl sebacate and dodecane diester; diesters of saturated aliphatic dicarboxylic acids and saturated aliphatic alcohols, such as distearyl ester and distearyl octadecanedioate; and diesters of saturated aliphatic diols and saturated aliphatic monocarboxylic acids, such as nonanediol dibehenate and dodecanediol distearate.
[0085] Among the ester waxes, a bifunctional ester wax (diester) having two ester bonds in the molecular structure may be contained. The bifunctional ester wax is an ester compound of a dihydric alcohol and an aliphatic monocarboxylic acid, or an ester compound of a dihydric carboxylic acid and an aliphatic monoalcohol.
[0086] Specific examples of aliphatic monocarboxylic acids include myristic acid, palmitic acid, stearic acid, arachidic acid, behenic acid, lignoceric acid, cerotic acid, montanic acid, melissic acid, oleic acid, vaccenic acid, linoleic acid, linolenic acid, etc. Specific examples of aliphatic monoalcohols include myristyl alcohol, cetanol, stearyl alcohol, arachidyl alcohol, behenyl alcohol, tetracosanol, hexacosanol, octacosanol, triacontanol, etc.
[0087] Specific examples of divalent carboxylic acids include butanedioic acid (succinic acid), pentanedioic acid (glutaric acid), hexanedioic acid (adipic acid), heptanedioic acid (pimelic acid), octanedioic acid (suberic acid), nonanedioic acid (azelaic acid), decanedioic acid (sebacic acid), dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, hexadecanedioic acid, octadecanedioic acid, eicosanediic acid, phthalic acid, isophthalic acid, and terephthalic acid. Specific examples of dihydric alcohols include ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,10-decanediol, 1,12-dodecanediol, 1,14-tetradecanediol, 1,16-hexadecanediol, 1,18-octadecanediol, 1,20-eicosanediol, 1,30-triacontanediol, diethylene glycol, dipropylene glycol, 2,2,4-trimethyl-1,3-pentanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, spiroglycol, 1,4-phenylene glycol, bisphenol A, and hydrogenated bisphenol A.
[0088] Other usable release agents include petroleum waxes and derivatives thereof such as paraffin wax, microcrystalline wax, and petrolatum; montan wax and derivatives thereof; hydrocarbon waxes and derivatives thereof produced by the Fischer-Tropsch process; polyolefin waxes and derivatives thereof such as polyethylene and polypropylene; natural waxes and derivatives thereof such as carnauba wax and candelilla wax; and fatty acids and compounds thereof such as higher aliphatic alcohols, stearic acid, and palmitic acid.
[0089] The content of the release agent is preferably 5.0 parts by mass or more and 20.0 parts by mass or less with respect to 100.0 parts by mass of the binder resin.
[0090] The toner particles may contain a colorant. The colorant is not particularly limited, and known colorants such as those shown below can be used.
[0091] Examples of yellow pigments that can be used include condensed azo compounds such as yellow iron oxide, navel yellow, naphthol yellow S, Hansa yellow G, Hansa yellow 10G, benzidine yellow G, benzidine yellow GR, quinoline yellow lake, permanent yellow NCG, and tartrazine lake, isoindolinone compounds, anthraquinone compounds, azo metal complexes, methine compounds, and allylamide compounds. Specific examples include the following. CI Pigment Yellow 12, 13, 14, 15, 17, 62, 74, 83, 93 , 94, 95, 109, 110, 111, 128, 129, 147, 155, 168, 180.
[0092] Examples of red pigments include condensed azo compounds such as red iron oxide, permanent red 4R, lithol red, pyrazolone red, watching red calcium salt, lake red C, lake D, brilliant carmine 6B, brilliant carmine 3B, eosin lake, rhodamine lake B, and alizarin lake, diketopyrrolopyrrole compounds, anthraquinone compounds, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds. Specific examples include the following. CI Pigment Red 2, 3, 5, 6, 7, 23, 48:2, 48:3, 48:4, 57:1, 81:1, 122, 144, 146, 166, 169, 177, 184, 185, 202, 206, 220, 221, 254.
[0093] Examples of blue pigments include copper phthalocyanine compounds and derivatives thereof such as alkali blue lake, Victoria blue lake, phthalocyanine blue, metal-free phthalocyanine blue, phthalocyanine blue partial chloride, fast sky blue, and indanthrene blue BG, anthraquinone compounds, and basic dye lake compounds. Specific examples include the following. CI Pigment Blue 1, 7, 15, 15:1, 15:2, 15:3, 15:4, 60, 62, 66.
[0094] Examples of black pigments include carbon black and aniline black.
[0095] These colorants may be used alone or in combination, or may be used in the form of a solid solution. The content of the colorant is preferably 3.0 parts by mass or more and 15.0 parts by mass or less relative to 100.0 parts by mass of the binder resin.
[0096] The toner particles may contain a charge control agent. Any known charge control agent can be used as the charge control agent. In particular, a charge control agent that can charge quickly and stably maintain a constant charge amount is preferred. Examples of charge control agents that control toner particles to be negatively charged include the following: organic metal compounds and chelating compounds, such as monoazo metal compounds, acetylacetone metal compounds, aromatic oxycarboxylic acids, aromatic dicarboxylic acids, oxycarboxylic acids, and dicarboxylic acid-based metal compounds; other examples include aromatic oxycarboxylic acids, aromatic mono- and polycarboxylic acids and their metal salts, anhydrides, or esters, and phenol derivatives such as bisphenol; and further examples include urea derivatives, metal-containing salicylic acid compounds, metal-containing naphthoic acid compounds, boron compounds, quaternary ammonium salts, and calixarenes.
[0097] On the other hand, examples of charge control agents that control toner particles to have a positive charge include the following: nigrosine and nigrosine modified with fatty acid metal salts; guanidine compounds; imidazole compounds; quaternary ammonium salts such as tributylbenzylammonium-1-hydroxy-4-naphthosulfonate and tetrabutylammonium tetrafluoroborate, and onium salts such as phosphonium salts analogous thereto, and lake pigments thereof; triphenylmethane dyes and lake pigments thereof (lake agents include phosphotungstic acid, phosphomolybdic acid, phosphotungstomolybdic acid, tannic acid, lauric acid, gallic acid, ferricyanide, ferrocyanide, etc.); metal salts of higher fatty acids; and resin-based charge control agents.
[0098] These charge control agents may be contained alone or in combination of two or more. The amount of these charge control agents added is preferably 0.01 parts by mass or more and 10.00 parts by mass or less per 100.00 parts by mass of the polymerizable monomer.
[0099] Methods for measuring various physical properties of the cleaning blade of the present disclosure will be described below. [Method of measuring elastic modulus] The elastic modulus using SPM is measured by the following method: The scanning probe microscope (SPM) used is MFP-3D-Origin (Oxford Instruments, Ltd.). The measurement samples are prepared as follows. With each of P1 to P9 as the center of gravity, a square measurement sample with a side of 2 mm is cut out, with one side parallel to the first line segment. Next, from each measurement sample, a cryomicrotome (UC-6 (product name), manufactured by Leica Microsystems) is used to cut out a polyurethane flake with a thickness of 200 nm and a size of 100 μm × 100 μm, with each of P1 to P9 as the center of gravity and one side parallel to the first line segment, at -150°C. Then, each of the obtained measurement samples is placed on a smooth silicon wafer and left to stand for 24 hours in an environment of room temperature of 25°C and relative humidity of 50%.
[0100] Next, the silicon wafer with the measurement sample placed on it is set on the SPM stage and observed with the SPM. Note that the spring constant and involute constant of the probe (product name: AC160, manufactured by Olympus Corporation) are confirmed in advance to be as follows for the thermal noise method installed in this SPM device. Spring constant: 30.22nN / nm Involve constant: 82.59 nm / V Furthermore, the probe is tuned in advance to determine the resonance frequency of the probe. Resonant frequency of the probe: 285KHz (1st order) and 1.60MHz (higher order) The measurement mode of the SPM is AM-FM mode, the free amplitude of the probe is 3 V (1st order) and 25 mV (higher order), and the set point amplitude is 2 V (1st order) and 25 mV (higher order). In a square field of view of 70 μm × 70 μm, scanning is performed at a scan speed of 1 Hz with 256 vertical and 256 horizontal scan points to simultaneously acquire height and phase images. Note that the field of view is selected so that each of P1 to P9 of each measurement sample is in the center of the field of view and one side is parallel to the first line segment. Then, from the height image and phase image obtained, the locations on the measurement sample where the elastic modulus is measured by force curve measurement are specified. That is, 70 points are specified at 1 μm pitch (interval) on the first line segment with each of P1 to P9 as the center, for a total of 630 points. Then, the force curve measurement in contact mode is performed once for each of the 630 points.
[0101] The force curves were obtained under the following conditions. In measuring the force curve, the piezoelectric element (Z piezo), which drives the probe, is controlled so that the probe turns back when the deflection of the probe reaches a certain value due to the tip touching the sample surface. The turning point at this time is called the trigger value, and indicates how much the voltage must increase from the deflection voltage at the start of the force curve to make the probe turn back. In this measurement, the force curve was measured with a trigger value of 0.2V. Other conditions for measuring the force curve are as follows: the distance from the tip position of the probe in the standby state to the point where the probe turns back at the trigger value is 500 nm, and the scan speed is 1 Hz (the speed at which the probe makes one round trip). Then, the obtained force curves are fitted one by one based on Hertz theory to calculate the elastic modulus. The elastic modulus (Young's modulus) according to Hertz theory is calculated using the following formula (*1).
[0102] Calculation formula (*1) F=(4 / 3)E * R 1 / 2 d 3 / 2 where F is the force applied to the sample by the tip at the tip return point, E * is the composite elastic modulus, R is the radius of curvature of the tip of the probe (8 nm), and d is the deformation of the sample at the point where the probe turns back.
[0103] Then, d is calculated using the following formula (*2). Calculation formula (*2) Calculate as d=Δz-D. Δz is the displacement of the piezoelectric element from when the tip of the probe comes into contact with the sample until it turns back, and D is the amount of warping of the probe at the time when it turns back. And, D is calculated using the following formula (*3).
[0104] Calculation formula (*3) D = α ΔV deflection In the formula (*3), α is the Involve constant of the probe, ΔV deflection represents the amount of change in the deflection voltage from when the probe starts to contact the sample to the turning point.
[0105] Furthermore, F is calculated using the following formula (*4). Calculation formula (*4) F=κ·D κ is the spring constant of the probe. ΔV deflectionSince and Δz are actual measured values, from formulas (*1) to (*4), E in formula (*1) * Furthermore, the desired elastic modulus (Young's modulus) Es can be calculated using the following formula (*5).
[0106] Calculation formula (*5) 1 / E * =[(1-Vs 2 ) / Es]-[(1-Vi 2 ) / Ei] Vs: Poisson's ratio of the sample (fixed at 0.33 in this embodiment) Vi: Poisson's ratio of the tip of the probe (in this example, the value for silicon is used) Ei: Young's modulus of the tip of the probe (in this embodiment, the value of silicon is used)
[0107] The average value of the elastic modulus calculated from the force curve at 70 points and 9 locations, a total of 630 points, was taken as the elastic modulus. The standard deviation was calculated from the elastic modulus at a total of 630 points. The coefficient of variation was calculated from the average value and the standard deviation. The values calculated in the examples are shown in Table 1.
[0108] [Method of measuring Martens hardness] The Martens hardness is measured by the following method. Assuming that a first line segment is drawn on the tip surface of the elastic member parallel to the tip edge, at a distance of 10 μm from the tip edge and of the same length as the tip edge, the length of the first line segment is L, and the Martens hardness measured on the first line segment at a point (5 / 10)L from one end of the first line segment, i.e., at the position P5, is HM1. Assuming that a bisector of the angle between the main surface and the tip surface is drawn on a cross section of the elastic member that is perpendicular to the tip surface and the tip edge including P5, the Martens hardness of the elastic member measured at a position on the bisector that is 500 μm away from the tip edge is defined as HM2 (see FIG. 6). The values of |HM2-HM1| measured in the examples are shown in Table 2. Microhardness tester: Shimadzu Corporation DUH-211S Measurement environment: 23±5℃ Measuring indenter: triangular pyramid indenter 115° (ridge angle 115°) Measurement mode: Depth setting test Depth setting: 2μm Load speed: 0.03mN / s Holding time: 5s Calculation formula: Martens hardness = 1000F / 26.43h 2 [N / mm 2 〕 F: test force (mN), h: indentation depth (μm)
[0109] Methods for measuring various physical properties of the toner of the present disclosure will be described below. <Method for measuring the number-average particle size (D1) of primary particles of external additives> The number average particle size (D1) of the primary particles of the external additive from the toner is calculated from an image of the external additive on the surface of the toner particles taken with a scanning electron microscope "S-4800" (product name; manufactured by Hitachi, Ltd.). The image taking conditions for the S-4800 are as follows. (1) Sample preparation Apply a thin layer of conductive paste to a sample stage (aluminum sample stage 15 mm x 6 mm) and spray toner onto it. Then use air to remove excess toner from the sample stage and dry thoroughly. Set the sample stage in the sample holder and adjust the sample stage height to 36 mm using the sample height gauge. (2) S-4800 observation condition setting The number average particle size of the primary particles of the external additive is calculated using an image obtained by backscattered electron image observation with the S-4800. Backscattered electron images have less charge-up of the external additive than secondary electron images, so the particle size of the external additive can be measured with high accuracy. Pour liquid nitrogen into the anti-contamination trap attached to the S-4800 housing until it overflows, and leave it for 30 minutes. Start the S-4800's "PC-SEM" and perform flushing (cleaning the FE chip, which is the electron source). Click the accelerating voltage display area on the control panel on the screen, and press the [Flushing] button to open the flushing execution dialog. Confirm that the flashing intensity is 2 and execute it. Confirm that the emission current due to flashing is 20μA~40μA. Insert the sample holder into the sample chamber of the S-4800 case. Press [Origin] on the control panel to move the sample holder to the observation position. Click the accelerating voltage display to open the HV setting dialog, and set the accelerating voltage to [0.8kV] and the emission current to [20μA]. In the [Basic] tab of the operation panel, set the signal selection to [SE], select [Upper (U)] and [+BSE] for the SE detector, and select [LA100] in the selection box to the right of [+BSE] to set the mode to observation using backscattered electron images. Similarly, in the [Basic] tab of the operation panel, set the probe current in the electron optical system condition block to [Normal], the focus mode to [UHR], and the WD to [3.0 mm]. Press the [ON] button in the acceleration voltage display section of the control panel to apply the acceleration voltage. (3) Calculation of the number-average particle diameter (D1) of the external additive ("da") used to calculate the theoretical coverage Drag within the magnification display on the control panel to set the magnification to 50,000 (50k). Rotate the focus knob [COARSE] on the operation panel to adjust the aperture alignment once the image is in focus to a certain extent. Click [Align] on the control panel to display the alignment dialog and select [Beam]. Rotate the STIGMA / ALIGNMENT knobs (X,Y) on the operation panel to move the displayed beam to the center of the concentric circles. Next, select [Aperture] and turn the STIGMA / ALIGNMENT knobs (X, Y) one by one to stop the image movement or to minimize the movement. Close the shutter and use the autofocus to adjust the focus. Repeat this process two more times to adjust the focus. Then, the particle diameters of 100 external additive particles on the surface of the toner particles are measured to obtain the average particle diameter. Since some external additive particles exist as aggregates, the maximum diameter of particles that can be confirmed as primary particles is obtained, and the number-average particle diameter (D1) of the primary particles of the external additive is obtained by arithmetically averaging the obtained maximum diameters. In addition, when multiple types of external additives are used, elemental analysis is performed in advance using an energy dispersive X-ray analyzer (EDAX) to identify the types of external additives on the toner surface, and then the number average particle size of the primary particles of each external additive is determined. If it is difficult to calculate the number-average particle size by the surface observation method, the number-average particle size of each external additive measured in advance may be used. In that case, the external additive alone is observed under a transmission electron microscope, and the major axis of 100 particles is measured to obtain the number-average particle size.
[0110] <Method for measuring adhesion rate of external additives> Add 160 g of sucrose (Kishida Chemical) to 100 mL of ion-exchanged water and dissolve in a hot water bath to prepare a concentrated sucrose solution. Add 31 g of the concentrated sucrose solution and 6 mL of Contaminon N (a 10% aqueous solution of a pH 7 neutral detergent for cleaning precision measuring instruments, consisting of nonionic surfactants, anionic surfactants, and organic builders, manufactured by Wako Pure Chemical Industries, Ltd.) to a centrifuge tube (volume 50 ml) to prepare a dispersion. Add 1.0 g of toner to this dispersion and break up the toner clumps with a spatula or similar. The centrifuge tube is shaken in a shaker at 350 strokes per minute (spm) for 20 minutes. After shaking, the solution is transferred to a glass tube for a swing rotor (50 mL capacity) and separated in a centrifuge (H-9R, manufactured by Kokusan Co., Ltd.) at 3500 rpm for 30 minutes. Visually check that the toner and aqueous solution are sufficiently separated, and collect the toner separated in the top layer with a spatula or similar. The collected aqueous solution containing the toner is filtered with a vacuum filter, and then dried in a dryer for at least 1 hour. The dried product is crushed with a spatula, and the amount of silicon is measured using fluorescent X-rays. The adhesion rate (%) is calculated from the ratio of the amount of the measured element between the toner after washing with water and the initial toner. The measurement of fluorescent X-rays for each element conforms to JIS K 0119-1969, and specifically, is as follows. The measurement equipment used is a wavelength dispersive X-ray fluorescence analyzer "Axios" (PANalytical) and the accompanying dedicated software "SuperQ ver.4.0F" (PANalytical) for setting measurement conditions and analyzing measurement data. Rh is used as the anode of the X-ray tube, the measurement atmosphere is vacuum, the measurement diameter (collimator mask diameter) is 10 mm, and the measurement time is 10 seconds. In addition, detection is performed with a proportional counter (PC) when measuring light elements, and a scintillation counter (SC) when measuring heavy elements. The measurement sample is prepared by placing about 1 g of washed toner in a 10 mm diameter aluminum ring for a special press, flattening it, and pressing it at 20 MPa for 60 seconds using a tablet press "BRE-32" (Maekawa Test Machinery Manufacturing Co., Ltd.) to form a pellet with a thickness of about 2 mm. Pellets are prepared using the same procedure, substituting the washed toner for the initial toner. Measurements are performed under the above conditions, and elements are identified based on the peak positions of the obtained X-rays, and their concentrations are calculated from the counting rate (unit: cps), which is the number of X-ray photons per unit time.
[0111] The quantitative determination method in the toner will be explained using silicon as an example. Silica (SiO2) fine powder is added to 100 parts by mass of toner particles so that the amount is 0.5 parts by mass, and mixed thoroughly using a coffee mill. In the same manner, silica fine powder is mixed with 100 parts by mass of toner particles so that the amount is 2.0 parts by mass and 5.0 parts by mass, respectively, and these are used as samples for the calibration curve. For each sample, pellets for the calibration curve were prepared using a tablet press as described above, and the diffraction peaks were measured when polyethylene terephthalate (PET) was used as the analyzing crystal. The count rate (unit: cps) of Si-Kα rays observed at angle (2θ) = 109.08° is measured. The acceleration voltage and current of the X-ray generator are set to 24 kV and 100 mA, respectively. A linear calibration curve is obtained by plotting the obtained X-ray count rate on the vertical axis and the amount of SiO2 added in each calibration curve sample on the horizontal axis. Next, the count rate of the Si-Kα radiation is measured using the pellets of the toner to be analyzed. The silicon content in the toner is then calculated from the above calibration curve. The ratio of the silicon content of the toner treated with the above dispersion to the silicon content of the initial toner calculated by the above method is calculated and used as the adhesion rate (%).
[0112] Next, titanium will be taken as an example. 0.5 parts by mass of titanium oxide (TiO2) fine powder is added to 100 parts by mass of toner particles, and mixed thoroughly using a coffee mill. Similarly, 2.0 parts by mass and 5.0 parts by mass of titanium oxide are mixed with 100 parts by mass of toner particles, respectively, and these are used as samples for the calibration curve. For each sample, a pellet of the calibration curve sample is prepared as described above using a tablet molding compression machine, and the count rate (unit: cps) of Ti-Kα rays observed at a diffraction angle (2θ) = 109.08° when polyethylene terephthalate (PET) is used as the analyzing crystal is measured. In this case, the acceleration voltage and current value of the X-ray generator are 24 kV and 100 mA, respectively. A linear calibration curve is obtained by plotting the obtained X-ray count rate on the vertical axis and the amount of TiO2 added in each calibration curve sample on the horizontal axis. Next, the count rate of Ti-Kα radiation is measured using the toner pellets to be analyzed. The titanium content in the toner is then calculated from the calibration curve. The ratio of the titanium content of the toner treated with the dispersion liquid to the titanium content of the initial toner calculated by the method described above is calculated and used as the adhesion rate (%).
[0113] <Method of measuring weight average particle size (D4) of toner> The weight average particle diameter (D4) of the toner is measured with an effective measurement channel count of 25,000 channels using a precision particle size distribution measuring device equipped with a 100 μm aperture tube and a fine hole electrical resistance method called "Coulter Counter Multisizer3" (registered trademark, manufactured by Beckman Coulter, Inc.) and the accompanying dedicated software "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.) for setting measurement conditions and analyzing measurement data, and then the weight average particle diameter (D4) is calculated by analyzing the measurement data. The electrolyte solution used for the measurements is made by dissolving special grade sodium chloride in ion-exchanged water to a concentration of approximately 1% by mass; specifically, "ISOTON II" (manufactured by Beckman Coulter) is used. Before performing measurements and analysis, the dedicated software is set up as follows. In the "Change Standard Measurement Method (SOM) screen" of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using "Standard Particle 10.0 μm" (Beckman Coulter). Press the threshold / noise level measurement button to automatically set the threshold and noise level. In addition, set the current to 1600 μA, the gain to 2, the electrolyte to ISOTON II, and check the aperture tube flush after measurement. In the "Pulse to particle size conversion setting screen" of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bins, and the particle size range from 2 μm to 60 μm.
[0114] The specific measurement method is as follows. (1) Pour about 200 ml of the electrolyte solution into a 250 ml round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, use the "Aperture Tube Flush" function of the dedicated software to remove dirt and air bubbles from inside the aperture tube. (2) Place about 30 ml of the electrolyte solution in a 100 ml flat-bottom glass beaker. As a dispersant, add approximately 0.3 ml of a diluted solution of "Contaminon N" (a 10% by weight aqueous solution of a neutral detergent for cleaning precision measuring instruments with a pH of 7 consisting of a nonionic surfactant, an anionic surfactant, and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) diluted 3 times by weight with ion-exchanged water. (3) A predetermined amount of ion-exchanged water is placed in the water tank of an ultrasonic disperser "Ultrasonic Dispersion System Tetora150" (manufactured by Nikkaki Bios Co., Ltd.) that has two oscillators with an oscillation frequency of 50 kHz built in with a phase shift of 180 degrees and an electrical output of 120 W, and approximately 2 ml of the Conaminon N is added to this water tank. (4) The beaker (2) is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the electrolyte solution in the beaker is maximized. (5) While the electrolyte solution in the beaker in (4) is irradiated with ultrasonic waves, about 10 mg of toner is added little by little to the electrolyte solution and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. During ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be 10°C or higher and 40°C or lower. (6) The (5) electrolyte solution in which the toner is dispersed is dropped into the (1) round-bottom beaker placed in the sample stand using a pipette to adjust the measurement concentration to about 5%. Then, measurements are continued until the number of particles measured reaches 50,000. (7) The measurement data is analyzed using the dedicated software that comes with the device, and the weight-average particle size (D4) is calculated. Note that when the dedicated software is set to Graph / Volume%, the "Arithmetic diameter" on the Analysis / Volume Statistics (Arithmetic Mean) screen is the weight-average particle size (D4).
[0115] <Method of measuring true density of toner and external additives> The true density of the toner and the external additive is measured using a dry automatic density meter "AccuPic 1330" manufactured by Shimadzu Corporation, in accordance with the operation manual of the device.
[0116] <Method for separating external additives from toner particles> If the external additive used for external addition is available, it may be used to carry out the above measurement. When the external additive separated from the surface of the toner particles is used as the measurement sample, the external additive is separated from the toner particles by the following procedure.
[0117] (1) Magnetic toner First, 6 mL of Contaminon N (a 10% by weight aqueous solution of a neutral detergent for cleaning precision measuring instruments, consisting of a nonionic surfactant, an anionic surfactant, and an organic builder, pH 7, manufactured by Wako Pure Chemical Industries, Ltd.) is added to 100 mL of ion-exchanged water to prepare a dispersion medium. 5 g of toner is added to this dispersion medium, and dispersed for 5 minutes using an ultrasonic disperser (As One Corporation VS-150). After that, the mixture is set in a "KM Shaker" (model: V.SX) manufactured by Iwaki Sangyo Co., Ltd., and shaken for 20 minutes at 350 strokes per minute. The toner particles are then held down using a neodymium magnet, and the supernatant is collected. The supernatant is then dried to collect the external additives. If a sufficient amount of external additives cannot be collected, this process is repeated. When a plurality of kinds of external additives are used, the external additives may be selected from the collected external additives by using a centrifugal separation method or the like.
[0118] (2) In the case of non-magnetic toner Add 160g of sucrose (Kishida Chemical) to 100mL of ion-exchanged water and dissolve in a hot water bath to prepare a concentrated sucrose solution. Place 31g of the concentrated sucrose solution and 6mL of Contaminon N in a centrifuge tube to prepare a dispersion. Add 1g of toner to this dispersion and break up any clumps of toner with a spatula or similar. The centrifugation tube is shaken for 20 minutes in the shaker at 350 reciprocations per minute. After shaking, the solution is transferred to a glass tube (50 mL) for a swing rotor and centrifuged. Centrifugation is performed at 3500 rpm for 30 minutes using a centrifugal separator (H-9R; manufactured by Kokusan Co., Ltd.). After centrifugation, the toner is present in the top layer in the glass tube, and the external additive is present in the aqueous solution in the lower layer. The aqueous solution in the lower layer is sampled and centrifuged to separate the sucrose and the external additive, and the external additive is collected. Centrifugation is repeated as necessary to thoroughly separate the dispersion, after which the dispersion is dried and the external additive is collected. As in the case of magnetic toner, when a plurality of types of external additives are used, the external additives are selected from the collected external additives by using a centrifugal separation method or the like. EXAMPLES
[0119] The present disclosure will be described in more detail below with reference to examples and comparative examples, but the present disclosure is in no way limited thereto. The number of parts used in the examples is based on mass unless otherwise specified.
[0120] [Example of toner particle production] <Production Example of Toner Particle 1> A production example of the toner particles 1 will be described.
[0121] <Preparation of binder resin particle dispersion> 89.5 parts of styrene, 9.2 parts of butyl acrylate, 1.3 parts of acrylic acid, and 3.2 parts of n-lauryl mercaptan were mixed and dissolved. An aqueous solution of 1.5 parts of Neogen RK (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) and 150 parts of ion-exchanged water was added to this solution and dispersed. An aqueous solution of 0.3 parts of potassium persulfate dissolved in 10 parts of ion-exchanged water was added while slowly stirring for 10 minutes. After nitrogen replacement, emulsion polymerization was performed at 70°C for 6 hours. After the polymerization was completed, the reaction solution was cooled to room temperature and ion-exchanged water was added to obtain a binder resin particle dispersion having a solid content concentration of 12.5% by mass and a median diameter based on volume of 0.2 μm.
[0122] <Preparation of release agent dispersion> 100 parts of a release agent (behenyl behenate, melting point: 72.1°C) and 15 parts of Neogen RK were mixed with 385 parts of ion-exchanged water, and dispersed for about 1 hour using a wet jet mill JN100 (manufactured by Jokou Co., Ltd.) to obtain a release agent dispersion. The concentration of the release agent in the release agent dispersion was 20% by mass.
[0123] <Preparation of Colorant Dispersion> As a colorant, 100 parts of carbon black "Nipex35 (manufactured by Orion Engineered Carbons)" and 15 parts of Neogen RK were mixed with 885 parts of ion-exchanged water, and dispersed for about 1 hour using a wet jet mill JN100 to obtain a colorant dispersion.
[0124] <Preparation of Toner Particle 1> 265 parts of binder resin particle dispersion, 10 parts of release agent dispersion, and 10 parts of colorant dispersion were dispersed using a homogenizer (IKA Ultra Turrax T50). The temperature inside the container was adjusted to 30°C while stirring, and 1 mol / L hydrochloric acid was added to adjust the pH to 5.0. After leaving it for 3 minutes, the temperature was raised to 50°C to generate associated particles. In this state, the particle size of the associated particles was measured using a Coulter Counter Multisizer 3 (registered trademark, manufactured by Beckman Coulter, Inc.). When the weight average particle size reached 6.2 μm, a 1 mol / L aqueous solution of sodium hydroxide was added to adjust the pH to 8.0 to stop particle growth. Thereafter, the temperature was raised to 95° C. to fuse and spheronize the associated particles. When the average circularity reached 0.980, the temperature was lowered to 30° C. to obtain toner particle dispersion 1. Hydrochloric acid was added to the obtained toner particle dispersion liquid 1 to adjust the pH to 1.5 or less, and the mixture was left to stand with stirring for 1 hour, after which the mixture was subjected to solid-liquid separation using a pressure filter to obtain a toner cake. The reslurry and solid-liquid separation were repeated until the electrical conductivity of the filtrate became 5.0 μS / cm or less, and then the solid-liquid separation was finally performed to obtain a toner cake. The obtained toner cake was dried using a flash jet dryer (manufactured by Seishin Enterprises). The drying conditions were an inlet temperature of 90°C, a dryer outlet temperature of 40°C, and the toner cake supply speed was adjusted according to the moisture content of the toner cake so that the outlet temperature did not deviate from 40°C. Furthermore, fine and coarse powders were removed using a multi-division classifier utilizing the Coanda effect, and toner particles 1 were obtained.
[0125] <Silica fine particles> The following silica particles were used: (Silica Microparticles 1) Dry silica fine powder [BET specific surface area 300m 2 / g] 100 parts of dimethyl silicone oil (viscosity 100 mm 2 Hydrophobization treatment was performed using 25 parts of hexane / s. (Silica Microparticles 2) Dry silica fine powder [BET specific surface area 150m 2 / g] 100 parts of dimethyl silicone oil (viscosity 100 mm 2 Hydrophobization treatment was performed using 20 parts of ethyl acetate / s. (Silica Microparticles 3) Dry silica fine powder [BET specific surface area 90m 2 / g], 2 parts of hexamethyldisilazane (HMDS) and dimethyl silicone oil (viscosity 100 mm 2 Hydrophobization treatment was performed using 10 parts of 100 parts of 100% ethyl alcohol / s. (Silica Microparticles 4) Dry silica fine powder [BET specific surface area 50m 2 A hydrophobic treatment was performed with 1.2 parts of hexamethyldisilazane (HMDS) per 100 parts of the polymer (w / g).
[0126] [Toner Production Example] <Toner 1 Manufacturing Example> The toner particles 1 obtained in Toner Particle Production Example 1 were subjected to an external addition mixing treatment using the device shown in FIG. In this embodiment, in the apparatus shown in FIG. 8, the diameter of the inner circumference of the main casing 1 is 130 mm, and the volume of the processing space 9 is 2.0×10 -3 m 3 The device used was a rated power of 5.5 kW for the drive unit 8, and the shape of the stirring member 20 was as shown in Fig. 9. The overlap width d of the stirring member 20a and the stirring member 20b in Fig. 9 was set to 0.25D with respect to the maximum width D of the stirring member 20, and the clearance between the stirring member 20 and the inner circumference of the main casing 1 was set to 3.0 mm. In the above-mentioned apparatus configuration, 100 parts of toner particles 1 and 2.5 parts of silica fine particles 2 were put into the apparatus shown in FIG. After the toner particles and silica fine particles were added, pre-mixing was performed to uniformly mix the toner particles and silica fine particles. The pre-mixing conditions were a power of 0.1 W / g (rotation speed of 150 rpm) of the drive unit 8 and a processing time of 1 minute. After the pre-mixing, the external addition mixing process was carried out. The external addition mixing process conditions were that the power of the drive unit 8 was constant at 0.6 W / g (the rotation speed of the drive unit 8 was 1400 rpm), the peripheral speed of the outermost end of the stirring member 3 was adjusted, and the processing time was 5 minutes. After the external additive mixing process, coarse particles were removed using a circular vibrating sieve equipped with a screen with a diameter of 500 mm and an opening of 75 μm to obtain Toner 1. Toner 1 was observed under a scanning electron microscope and the number average particle size of the primary particles of the silica fine particles on the toner surface was measured to be 15 nm. The external additive conditions and physical properties of Toner 1 are shown in Table 1.
[0127] <Production Examples of Toners 2 to 12> Toners 2 to 12 were obtained in the same manner as in Production Example of Toner 1, except that in Production Example of Toner 1, the type and amount of silica fine particles added, and external addition conditions were changed as shown in Table 1. The hydrotalcite compound used in Toner 9 was DHT-4A manufactured by Kyowa Chemical Industry Co., Ltd. In Toner 9, 0.2 parts of the hydrotalcite compound was added together with the silica fine particles to 100 parts of toner particles 1, and external addition was performed using the device shown in FIG. Further, for toner 12, a Henschel mixer (product name) was used as the external addition device instead of the device shown in FIG. 8, and external addition was performed under the following conditions. Circumferential speed: 30m / s, mixing time: 10 minutes
[0128] [Table 1]
[0129] [Cleaning blade manufacturing example] <Manufacturing example of cleaning blade 1> <Supporting member> A galvanized steel plate having a thickness of 1.6 mm was prepared and processed to obtain a support member having an L-shaped cross section as shown by reference numeral 3 in FIG. An adhesive for bonding polyurethane resins (product name: Chemlock 219, manufactured by Lord Corporation) was applied to the portions of the support member that would come into contact with the elastic member.
[0130] <Preparation of raw materials for elastic members> 4,4'-Diphenylmethane Diisocyanate (Product name: Millionate MT, Tosoh ( (Hereinafter, Millionate MT will also be referred to as 4,4'-MDI) 345.5 copies Polymeric MDI (product name: Millionate MR-400, manufactured by Tosoh Corporation) (hereinafter, Millionate MR-400 will also be referred to as MR400) 20.0 parts Polyol (butylene adipate polyester polyol having a number average molecular weight of 2500, product name: Nipporan 3027, manufactured by Tosoh Corporation) (hereinafter, Nipporan 3027 will also be referred to as PBA2500) 634.5 parts The above materials were reacted at 80° C. for 3 hours to obtain a prepolymer having an NCO isocyanate content of 36.6% by weight.
[0131] Next, the following materials were mixed to prepare a hardener. 1,4-butanediol (manufactured by Tokyo Chemical Industry Co., Ltd.) (hereinafter, 1,4-butanediol is also referred to as 1,4-BD) 7.0 parts Triol (glycerin manufactured by Tokyo Chemical Industry Co., Ltd.) 42.2 parts Polyol (hexylene adipate polyester polyol having a number average molecular weight of 1000 (trade name: Nipponran 164, manufactured by Tosoh Corporation) (hereinafter, Nipponran 164 will also be referred to as PHA1000) 302.7 parts Polycat46 (product name, manufactured by Air Products Japan) 0.13 parts N,N'-Dimethylhexanolamine (product name Kao Raiser No. 25, manufactured by Kao Corporation) (hereinafter, Kao Raiser No. 25 will also be referred to as No. 25) 0.55 parts
[0132] This mixture (curing agent) was added to the above prepolymer and mixed to obtain a polyurethane elastomer composition. The adhesive application portion of the support member was positioned so as to protrude into the cavity of a mold for forming a cleaning blade. The polyurethane elastomer composition was then poured into the mold for forming a cleaning blade, cured at 130°C for 2 minutes, and then removed from the mold to obtain an integrally molded product of polyurethane and the support member. Before injecting the polyurethane elastomer composition into the mold, the mold was coated with a release agent A. The release agent A was a mixture of the following materials.
[0133] ELEMENT14 PDMS 1000-JC (product name, manufactured by Momentive Performance Materials) 5.06 parts ELEMENT14 PDMS 10K-JC (product name, manufactured by Momentive Performance Materials) 6.19 parts SR1000 (product name, manufactured by Momentive Performance Materials) 3.75 copies EXXSOL DSP145 / 160 (product name, manufactured by Ando Parachemie Co., Ltd.) 85 copies
[0134] This integrally molded body was appropriately cut to an edge angle of 90 degrees, and the lengths in the short direction, thickness direction and length direction of the polyurethane were 7.5 mm, 1.8 mm and 240 mm, respectively. The physical properties of the obtained cleaning blade 1 are shown in Table 2.
[0135] <Manufacturing example of cleaning blade 2-3> Cleaning blades 2 and 3 were obtained in the same manner as cleaning blade 1, except that the composition of the prepolymer and the composition of the curing agent were changed as shown in Table 2. In Table 2, TMP stands for trimethylolpropane. The physical properties of the obtained cleaning blades 2 and 3 are shown in Table 2.
[0136] <Manufacturing example of cleaning blade 4> Cleaning blade 4 was obtained in the same manner as cleaning blade 2, except that the following post-treatment was carried out. The physical properties of cleaning blade 4 obtained are shown in Table 2. The obtained cleaning blade 2 was subjected to ultraviolet light with an intensity of 32.8 mW / cm 2 The ultraviolet irradiation was performed for 120 seconds using an ultraviolet irradiation treatment device with an integrated ultraviolet light dose of 3936 mJ / cm 2 The surface treatment was carried out.
[0137] <Manufacturing example of cleaning blade 5> A cleaning blade was obtained in the same manner as cleaning blade 1, except that the composition of the prepolymer and the composition of the curing agent were changed as shown in Table 2. In Table 2, PBA2000 indicates butylene adipate polyester polyol having a number average molecular weight of 2000 (product name: Nipporan 4010, manufactured by Tosoh Corporation). The obtained cleaning blade was subjected to secondary curing at 130°C for 60 minutes, and then 2 mm of the tip of the elastic member was immersed in 4,4'-MDI dissolved at 80°C for 10 seconds. After immersion, the 4,4'-MDI attached to the blade surface was washed with butyl acetate. After washing, the blade was aged for 24 hours to obtain a surface-treated cleaning blade 5. The physical properties of the obtained cleaning blade 5 are shown in Table 2.
[0138] <Manufacturing example of cleaning blade 6> A cleaning blade was obtained in the same manner as in cleaning blade 1, except that the composition of the prepolymer and the composition of the curing agent were changed as shown in Table 2. The obtained cleaning blade was irradiated with ultraviolet light at an intensity of 32.8 mW / cm. 2 The ultraviolet irradiation was performed for 150 seconds using an ultraviolet irradiation treatment device, with an integrated ultraviolet light dose of 4920 mJ / cm 2 The surface treatment was carried out to obtain a cleaning blade 6. The physical properties of the obtained cleaning blade 6 are shown in Table 2.
[0139] <Manufacturing example of cleaning blade 7> A polyurethane elastomer composition was obtained in the same manner as for cleaning blade 1, except that the composition of the prepolymer and the composition of the curing agent were changed as shown in Table 2. In Table 2, PBA2000 represents a butylene adipate polyester polyol having a number average molecular weight of 2000 (product name: Nipporan 4010, manufactured by Tosoh Corporation). A polyurethane elastomer composition was injected into a mold in the same manner as the cleaning blade 1, cured at 130 °C for 10 minutes, taken out of the mold, and then subjected to secondary curing at 130 °C for 60 minutes. A cleaning blade 7 was obtained in the same manner as the cleaning blade 1, except for this secondary curing. The physical properties of the obtained cleaning blade 7 are shown in Table 2.
[0140] <Production Example of Cleaning Blade 8> A polyurethane elastomer composition was obtained in the same manner as the cleaning blade 1, except that the composition of the prepolymer and the composition of the curing agent were changed as shown in Table 2. A polyurethane elastomer composition was injected into a mold in the same manner as the cleaning blade 1, cured at 130 °C for 10 minutes, taken out of the mold, and then subjected to secondary curing at 130 °C for 60 minutes to obtain an integrally molded body of polyurethane and a support member. The obtained integrally molded body was cut in the same manner as the cleaning blade 1, and the tip 2 mm of the elastic member was immersed in 4,4'-MDI melted at 80 °C for 10 seconds. After the immersion, the 4,4'-MDI adhering to the blade surface was washed with butyl acetate. After the washing, it was heated at 100 °C for 30 minutes and then aged for 24 hours to obtain a surface-treated cleaning blade 8. The physical properties of the obtained cleaning blade 8 are shown in Table 2.
[0141]
Table 2
[0142] 〔Examples 1 to 13, Comparative Examples 1 to 6〕 Using the obtained toners 1 to 12 and cleaning blades 1 to 8, evaluations were conducted by the evaluation methods described below. The toners, cleaning blades used in the examples and comparative examples, and the evaluation results are shown in Table 3.
[0143] <Evaluation with LBP> A modified model of a commercially available Canon laser beam printer LBP9950Ci was used. The modification points were to change the gears and software of the evaluation machine body to change the process speed to 3 The speed was changed to 30 mm / sec, and printing was possible only with the black station. The toner in the process cartridge of the LBP9950Ci was removed, the inside was cleaned with an air blower, and then 150 g of the toner to be evaluated was loaded. The cleaning blade to be evaluated was also incorporated into the process cartridge as a cleaning blade for the photoconductor, which is the member to be cleaned. The process cartridge was then left for 24 hours in a high temperature and high humidity environment (30°C / 80% RH). After leaving the process cartridge, it was attached to the black station of the LBP9950Ci and the following evaluations were performed.
[0144] <Evaluation of cleaning ability> In a high temperature and humidity environment (30°C / 80%RH), 10,000 sheets of A4 paper with a 1.0% print ratio were printed out in landscape orientation. After printing 10,000 sheets, the toner loading was 0.2 mg / cm 2 The halftone images were printed on five sheets and visually evaluated according to the following criteria. The evaluation results are shown in Table 3. A: No cleaning defects on the halftone image, no stains on the charging member. B: No cleaning defects on halftone image, dirt on charged member. C: A small amount of cleaning failure can be seen on the halftone image. D: Cleaning defects are noticeable on halftone images.
[0145] <Startup Line Evaluation> In a high temperature and humidity environment (30℃ / 80%RH), the recording medium is A4 size 75g / m 2 Using paper of 1000 mm diameter, 4.0% horizontal lines were printed out at 3000 sheets per day for a total of 9000 sheets over three days. After the 9000 sheets were printed, evaluation was carried out first thing in the morning on the fourth day. Specifically, five solid white images were printed out in succession, and the degree of start-up streaks was evaluated according to the following criteria. Furthermore, after leaving the printer for seven days under high temperature and high humidity conditions (30°C / 80% RH), five solid white images were printed out in succession in the same way, and the degree of start-up streaks was evaluated according to the following criteria. The evaluation results are shown in Table 3. A: No startup streaks are visible on the first solid white image. B: The startup streak can be faintly seen on the first solid white image. C: The starting lines can be faintly seen on the first solid white image, and the starting lines can also be faintly seen in the charged member cycle on the second and subsequent solid white images. D: A clear startup streak appears on the first solid white image, but on the second and subsequent solid white images, the startup streak is only faintly visible or not visible at all. E: Clear startup lines occur on the first solid white image, and startup lines also occur on the second and subsequent solid white images.
[0146] [Table 3] [Explanation of symbols]
[0147] 1: cleaning blade, 2: elastic member, 3: support member, 4: main surface facing member to be cleaned, 5: tip surface forming a tip edge together with the main surface, 6: electrophotographic photosensitive member, R: rotation direction of electrophotographic photosensitive member, 31: first line segment, 7: central axis, 8: drive unit, 9: processing space, 10: rotor end side, 11: rotation direction, 12: return direction, 13: feed direction, 16: inner piece for raw material inlet, 17: inner piece for product outlet, 18: main body casing, 19: rotor, 20, 20a, 20b: stirring member, 21: jacket, 22: raw material inlet, 23: product outlet
Claims
1. an electrophotographic photoreceptor having a support and a photosensitive layer on the support; a charging means for charging the surface of the electrophotographic photoreceptor; an exposure means for forming a latent image on the surface of the electrophotographic photoreceptor by irradiating the surface of the electrophotographic photoreceptor with exposure light; a developing means having a toner and for developing the latent image with the toner to form a toner image on the surface of the electrophotographic photoreceptor; a transfer means for transferring the toner image onto a transfer material; and Cleaning blade In an electrophotographic apparatus having The cleaning blade is An elastic member including polyurethane; A support member that supports the elastic member; Equipped with the cleaning blade is disposed so that a part of the elastic member is in contact with the surface of the electrophotographic photoreceptor, When the side of the cleaning blade that contacts the surface of the electrophotographic photoreceptor is defined as the tip side of the cleaning blade, The elastic member has at least the tip side, a main surface facing the surface of the electrophotographic photoreceptor; a tip surface which forms a tip edge together with the main surface; The plate shape has Assuming that a first line segment is drawn on the tip surface in parallel to the tip edge, at a distance of 10 μm from the tip edge, and having the same length as the tip edge, The length of the first line segment is L, On the first line segment, A point (1 / 10)L away from one end of the first line segment is called P1. A point (2 / 10)L from one end of the first line segment is called P2. A point (3 / 10)L from one end of the first line segment is called P3. A point (4 / 10)L from one end of the first line segment is called P4. A point (5 / 10)L from one end of the first line segment is called P5. A point (6 / 10)L from one end of the first line segment is called P6. A point (7 / 10)L from one end of the first line segment is called P7. A point (8 / 10)L from one end of the first line segment is called P8. When the point P9 is (9 / 10)L from one end of the first line segment, When a total of 630 points are taken on the first line segment with a pitch of 1 μm, with each of 70 points being taken around each of the points P1 to P9, the average value of the elastic modulus obtained by measuring the positions of each of the 630 points using a scanning probe microscope is 15 MPa or more and 470 MPa or less, and The coefficient of variation of the elastic modulus is 7.0% or less, The Martens hardness of the elastic member measured at the position P5 is defined as HM1, Assuming that a bisector of an angle between the main surface and the tip surface is drawn on a cross section of the elastic member perpendicular to the tip surface and the tip edge including P5, the Martens hardness of the elastic member measured at a position on the bisector that is 500 μm away from the tip edge is HM2, |HM1-HM2| is 0.30N / mm 2 is as follows: The toner contains toner particles and an external additive, The number average particle size of the primary particles of the external additive is 5 nm or more and 25 nm or less, a coverage ratio X1 of the surface of the toner particles by the external additive as measured by an X-ray photoelectron spectrometer is 50 area % or more and 85 area % or less; When the theoretical coverage rate of the surface of the toner particle by the external additive is X2, the diffusion index represented by the following formula (1) satisfies the following formula (2): (1) Diffusion index = X1 / X2 (2) Diffusion index ≧-0.0042×X1+0.60 Electrophotographic apparatus characterized in that
2. The electrophotographic apparatus according to claim 1 , wherein the external additive contains silica fine particles.
3. 3. The electrophotographic apparatus according to claim 1, wherein X1 is 60 area % or more and 80 area % or less.
4. The |HM1-HM2| is 0.10 N / mm 2 4. The electrophotographic apparatus according to claim 1, wherein:
5. 5. The electrophotographic apparatus according to claim 1, wherein a fixing rate F of the external additive to the toner particles is 75% or more.
6. 6. The electrophotographic apparatus according to claim 1, wherein the external additive further contains a hydrotalcite compound.
7. 7. The electrophotographic apparatus according to claim 1, wherein the diffusion index is from 0.51 to 0.56, and the value of -0.0042 x X1 + 0.60 is from 0.25 to 0.
35.
8. an electrophotographic photoreceptor having a support and a photosensitive layer on the support; a developing means having a toner and for forming a toner image on the surface of the electrophotographic photoreceptor by developing a latent image formed on the surface of the electrophotographic photoreceptor with the toner; and Cleaning blade A process cartridge which is detachably mountable to a main body of an electrophotographic apparatus, The cleaning blade is An elastic member including polyurethane; A support member that supports the elastic member; Equipped with the cleaning blade is disposed so that a part of the elastic member is in contact with the surface of the electrophotographic photoreceptor, When the side of the cleaning blade that contacts the surface of the electrophotographic photoreceptor is defined as the tip side of the cleaning blade, The elastic member has at least the tip side, a main surface facing the surface of the electrophotographic photoreceptor; a tip surface which forms a tip edge together with the main surface; The plate shape has Assuming that a first line segment is drawn on the tip surface in parallel to the tip edge, at a distance of 10 μm from the tip edge, and having the same length as the tip edge, The length of the first line segment is L, On the first line segment, A point (1 / 10)L away from one end of the first line segment is called P1. A point (2 / 10)L from one end of the first line segment is called P2. A point (3 / 10)L from one end of the first line segment is called P3. A point (4 / 10)L from one end of the first line segment is called P4. A point (5 / 10)L from one end of the first line segment is called P5. A point (6 / 10)L from one end of the first line segment is called P6. A point (7 / 10)L from one end of the first line segment is called P7. A point (8 / 10)L from one end of the first line segment is called P8. When the point P9 is (9 / 10)L from one end of the first line segment, When a total of 630 points are taken on the first line segment with a pitch of 1 μm, with each of 70 points being taken around each of the points P1 to P9, the average value of the elastic modulus obtained by measuring the positions of each of the 630 points using a scanning probe microscope is 15 MPa or more and 470 MPa or less, and The coefficient of variation of the elastic modulus is 7.0% or less, The Martens hardness of the elastic member measured at the position P5 is defined as HM1, Assuming that a bisector of an angle between the main surface and the tip surface is drawn on a cross section of the elastic member perpendicular to the tip surface and the tip edge including P5, the Martens hardness of the elastic member measured at a position on the bisector that is 500 μm away from the tip edge is HM2, |HM1-HM2| is 0.30N / mm 2 is as follows: The toner contains toner particles and an external additive, The number average particle size of the primary particles of the external additive is 5 nm or more and 25 nm or less, a coverage ratio X1 of the surface of the toner particles by the external additive as measured by an X-ray photoelectron spectrometer is 50 area % or more and 85 area % or less; When the theoretical coverage rate of the surface of the toner particle by the external additive is X2, the diffusion index represented by the following formula (1) satisfies the following formula (2): (1) Diffusion index = X1 / X2 (2) Diffusion index ≧-0.0042×X1+0.60 A process cartridge comprising:
Citation Information
Patent Citations
Blade for electrophotographic device, and method of manufacturing blade for electrophotographic device
JP2009244761A
Toner
JP2011047988A
Cleaning blade, image forming apparatus, and process cartridge
JP2014240946A
Process cartridge
JP2015011131A
toner
JP2015118177A